Bioelectrode composition, bioelectrode, and method for producing bioelectrode

By using a bioelectrode composition containing silicone T units, the problems of decreased conductivity of the bioelectrode and skin allergies under wet and dry conditions are solved, and a low-cost, high-conductivity and high adhesion bioelectrode material is achieved.

JP7627671B2Active Publication Date: 2025-02-06SHIN ETSU CHEMICAL CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2022049558
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-04-16
Filing Date
2022-03-25
Publication Date
2025-02-06
Estimated Expiration
2042-03-25

AI Technical Summary

Technical Problem

The existing bioelectrode materials are prone to decrease electrical conductivity, skin allergies and insufficient adhesion during long-term use, making it difficult to maintain stable electrical signal conduction under wet and dry conditions, and are costly to produce.

Method used

A bioelectrode composition is adopted that contains a silicone (RSiO3/2) structure bound to an ionic polymer, has a T unit, and contains a fluorosulfonate, a fluorosulfonimide and an N-carbonyl fluorosulfonamide plasma salt, and a soft, ductile and adhesion-friendly biological contact layer is formed by copolymerization and crosslinking reaction.

Benefits of technology

It achieves high conductivity and biocompatibility under both wet and dry conditions, reduces manufacturing costs, and bioelectrodes are not likely to cause skin allergies during long-term use, and can stabilize bioelectric signals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627671000173
    Figure 0007627671000173
  • Figure 0007627671000174
    Figure 0007627671000174
  • Figure 0007627671000175
    Figure 0007627671000175
Patent Text Reader

Abstract

To provide a bio-electrode composition capable of forming a living body contact layer for a bio-electrode having excellent electric conductivity, biocompatibility and light weight, manufactured at a low cost, even when being wetted or dried, preventing the conductivity from significantly lowering, being soft and having excellent elasticity and adhesion.SOLUTION: A bio-electrode composition contains (A) a silicone (R0SiO3 / 2) (T1) (in the formula, R0 represents a linking group with the ionic polymer) bonded to an ionic polymer and having a structure (excluding a cage structure) containing a T unit shown by the general formula (T1). The ionic polymer is a polymer containing a repeating unit having a structure selected from an ammonium salt, lithium salt, sodium salt, potassium salt and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonyl-fluorosulfonamide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a bioelectrode that can be brought into contact with the skin of a living body and detect a bodily condition such as heart rate by an electrical signal from the skin, a method for producing the same, and a bioelectrode composition that is suitably used for the bioelectrode. [Background technology]

[0002] In recent years, the development of wearable devices has progressed with the spread of IoT (Internet of Things). Typical examples are watches and glasses that can connect to the Internet. In addition, wearable devices that can constantly monitor the condition of the body are needed in the medical and sports fields, and these are expected to be growth fields in the future.

[0003] In the medical field, wearable devices that monitor the state of the body's organs by sensing weak currents, such as in electrocardiograms, which detect the movement of the heart through electrical signals, are being considered. In electrocardiograms, electrodes coated with conductive paste are attached to the body to perform the measurement, but this is a one-time, short-term measurement. In contrast, the aim of developing medical wearable devices such as those mentioned above is to develop devices that constantly monitor the health state for several weeks in a row. Therefore, the bioelectrodes used in medical wearable devices are required to have no change in conductivity even when used for long periods of time and to be free of skin allergies. In addition to these, they are also required to be lightweight and to be able to be manufactured at low cost.

[0004] Wearable medical devices include those that are attached to the body and those that are incorporated into clothing. As a type that is attached to the body, a bioelectrode that uses a water-soluble gel containing water and electrolytes, which are the materials for the conductive paste mentioned above, has been proposed (Patent Document 1). The water-soluble gel contains sodium, potassium, and calcium as electrolytes in a water-soluble polymer that holds water, and converts changes in ion concentration from the skin into electricity. On the other hand, as a type that is incorporated into clothing, a method has been proposed in which a conductive polymer such as PEDOT-PSS (Poly-3,4-ethylenedioxythiophene-Polystyrenesulfonate) or cloth with silver paste incorporated into the fibers is used as an electrode (Patent Document 2).

[0005] However, when using the above-mentioned water-soluble gel containing water and electrolytes, there is a problem that the conductivity is lost when the water dries out. On the other hand, when using metals with a high ionization tendency such as copper, there is a problem that some people may develop skin allergies, and when using conductive polymers such as PEDOT-PSS, there is a problem that the conductive polymer is highly acidic and therefore may develop skin allergies, and the conductive polymer may peel off from the fibers during washing.

[0006] In addition, because of their excellent electrical conductivity, the use of metal nanowires, carbon black, carbon nanotubes, and the like as electrode materials has also been considered (Patent Documents 3, 4, 5). Metal nanowires have a high probability of contact between wires, so they can conduct electricity with a small amount of additive. However, metal nanowires are thin materials with sharp tips, which can cause skin allergies. Thus, even if the material itself does not cause an allergic reaction, the shape and irritation of the material can cause the material to have poor biocompatibility, making it difficult to achieve both electrical conductivity and biocompatibility.

[0007] Metal films are highly conductive and one would think they would function as excellent bioelectrodes, but this is not necessarily the case. When the heart beats, not only a weak current is released from the skin, but also sodium ions, potassium ions, and calcium ions. For this reason, it is necessary to convert the change in ion concentration into an electric current, but precious metals, which are difficult to ionize, are inefficient at converting ions from the skin into an electric current. Therefore, bioelectrodes using precious metals have a high impedance, and there is a high resistance to electrical current passing through the skin.

[0008] On the other hand, batteries to which ionic liquids have been added are being considered (Patent Document 6). Ionic liquids are characterized by high thermal and chemical stability and excellent electrical conductivity, and are being widely used in batteries. However, since ionic liquids with small molecular weights as shown in Patent Document 6 dissolve in water, when a bioelectrode to which this has been added is used, the ionic liquid is extracted by sweat from the skin, which not only reduces electrical conductivity but also penetrates the skin and causes rough skin.

[0009] In addition, a battery using a lithium salt of a polymer-type sulfonimide is being studied (Non-Patent Document 1). However, although lithium is applied to batteries because of its high ion mobility, it is not a biocompatible material. Furthermore, a lithium salt of fluorosulfonic acid pendant on silicone is also being studied (Non-Patent Document 2).

[0010] When the bioelectrode is separated from the skin, it is no longer able to obtain information from the body. Furthermore, even a change in the contact area causes a fluctuation in the amount of electricity passing through, and the baseline of the electrocardiogram (electrical signal) fluctuates. Therefore, in order to obtain a stable electrical signal from the body, it is necessary for the bioelectrode to be in constant contact with the skin and for the contact area to remain constant. For this reason, it is preferable for the bioelectrode to have adhesive properties. It is also necessary for the bioelectrode to have elasticity and flexibility so that it can follow the expansion and contraction and bending changes of the skin.

[0011] A bioelectrode is being considered in which the part that comes into contact with the skin is made of silver chloride, and the part that conducts to the device is laminated with silver. Solid silver chloride has no adhesive power to the skin and is not elastic, so its ability to collect biosignals decreases, especially when the human body moves. For this reason, a laminated film of silver chloride and silver is used as a bioelectrode with a water-soluble gel laminated between the skin. In this case, the aforementioned gel will dry out and cause deterioration.

[0012] In recent years, bioelectrode compositions containing silsesquioxanes with pendant salts have been proposed. For example, bioelectrode compositions containing silsesquioxanes with pendant fluorosulfonate salts (Patent Document 7), bioelectrode compositions containing silsesquioxanes with pendant fluorosulfonimides (Patent Document 8), and bioelectrode compositions containing silsesquioxanes with pendant fluorosulfonamides (Patent Document 9).

[0013] The salts with high polarizability pendant silsesquioxane have high ionic conductivity and are highly sensitive as bioelectrodes. However, silsesquioxane is hard and has poor elasticity. For wearable device applications that are attached to elastic skin, the electrodes must be soft and highly elastic, as well as highly sensitive as bioelectrodes.

[0014] POSS R An ionic polymer in which is copolymerized is described in the Examples (Patent Documents 10, 11, and 12). POSS is a type of silsesquioxane, but has a hard cage structure, so in this case the adhesiveness does not increase.

[0015] A bioelectrode material has been proposed that is a mixture of an ionic polymer and soft polyurethane with pendant silsesquioxane (Patent Document 13). In this case, the silsesquioxane is formed after polymer polymerization, and has a ladder or random structure rather than a cage structure. The soft polyurethane with pendant ladder or random silsesquioxane has adhesive properties, which has the advantage of improving adhesion to the skin. [Prior art documents] [Patent documents]

[0016] [Patent Document 1] International Publication No. WO2013-039151 Brochure [Patent Document 2] JP 2015-100673 A [Patent Document 3] Japanese Patent Application Publication No. 5-095924 [Patent Document 4] JP 2003-225217 A [Patent Document 5] JP 2015-019806 A [Patent Document 6] Special Publication No. 2004-527902 [Patent Document 7] JP 2020-31722 A [Patent Document 8] JP 2020-28515 A [Patent Document 9] JP 2020-006069 A [Patent Document 10] JP 2018-99504 A [Patent Document 11] JP 2018-126496 A [Patent Document 12] JP 2018-130533 A [Patent Document 13] JP 2019-93118 A [Non-patent literature]

[0017] [Non-Patent Document 1] J.Mater.Chem.A,2016,4,p10038-10069 [Non-Patent Document 2] J. of the Electrochemical Society, 150(8) A1090-A1094 (2003) Summary of the Invention [Problem to be solved by the invention]

[0018] The present invention has been made to solve the above problems, and aims to provide a bioelectrode composition that can form a biocontact layer for a bioelectrode that is excellent in electrical conductivity and biocompatibility, lightweight, can be manufactured at low cost, does not significantly decrease in electrical conductivity whether wetted with water or dried, and is soft, stretchable, and adhesive; a bioelectrode in which a biocontact layer is formed from the bioelectrode composition; and a method for manufacturing the same. [Means for solving the problem]

[0019] In order to solve the above problems, the present invention provides A bioelectrode composition comprising: (A) A silicone bonded to an ionic polymer and having a structure (excluding a cage structure) containing a T unit represented by the following general formula (T1): (R 0 SiO 3 / 2 ) (T1) (In the formula, R 0 is a linking group to the ionic polymer. and The ionic polymer is a polymer having a repeating unit having a structure selected from the group consisting of ammonium salts, lithium salts, sodium salts, potassium salts, and silver salts of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide.

[0020] Such a bioelectrode composition can be used to form a biocontact layer for a bioelectrode that is excellent in electrical conductivity and biocompatibility, lightweight, and can be produced at low cost, and that does not significantly decrease in electrical conductivity whether wetted with water or dried, and that is soft, stretchable, and adhesive.

[0021] In addition, it is preferable that the repeating unit having a structure selected from the group consisting of the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide has a structure represented by any of the following general formulas (1)-1 to (1)-4. [ka] (In the formula, Rf1 and Rf2 are a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group. When Rf1 and Rf2 are oxygen atoms, Rf1 and Rf2 are one oxygen atom bonding to one carbon atom to form a carbonyl group. Rf3 and Rf4 are a hydrogen atom, a fluorine atom, or a trifluoromethyl group. At least one of Rf1 to Rf4 is a fluorine atom or a trifluoromethyl group. Rf5, Rf6, and Rf7 are a fluorine atom or a linear or branched alkyl group having 1 to 4 carbon atoms and having at least one fluorine atom. m is an integer of 1 to 4. M + is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion.

[0022] In addition, the repeating unit having a structure selected from the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide is preferably one or more types selected from repeating units (2-1) to (2-7) represented by the following general formula (2). [ka] (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R12 and R 14 R each independently represents a single bond, or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have either an ester group or an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 In the formula, one or two of the hydrogen atoms may be substituted with a fluorine atom. Each of X1, X2, X3, X4, X6, and X7 is independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, and X5 is a single bond, an ether group, or an ester group. Y is an oxygen atom, -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may be bonded to form a ring. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 each satisfy 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0≦a7≦1.0, <a1+a2+a3+a4+a5+a6+a7≦1.0である。M + is an ion selected from an ammonium ion, a lithium ion, a sodium ion, a potassium ion, and a silver ion. Rf5, Rf6, and Rf7 are a fluorine atom, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom.

[0023] If the ionic polymer has such a repeating unit, it becomes a bioelectrode composition that can form a biocontact layer that can obtain a biosignal in a short time after being attached to the body.

[0024] It is also preferred that the component (A) is a condensation reaction product of an ionic intermediate polymer in which, in addition to the repeating unit represented by the general formula (2), a repeating unit having an alkoxysilyl group represented by the following general formula (3) is copolymerized: [ka] (In the formula, R20 is a hydrogen atom or a methyl group, X8 is a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, R 21 R is a single bond, a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms, or a phenylene group, which may contain an oxygen atom or a nitrogen atom. 22 are the same or different alkyl groups having 1 to 4 carbon atoms. b1 is 0 <b1<1.0である。)

[0025] In this case, it is preferable that the condensation reaction product has a repeating unit represented by the following general formula (4). [ka] (In the formula, R 20 , X8, R 21 , and b1 are as described above.)

[0026] Such a component (A) can be easily synthesized.

[0027] In addition, the component (A) preferably contains, as the ammonium ion constituting the ammonium salt, an ammonium ion represented by the following general formula (5). [ka] (In the formula, R 101d , R 101e , R 101f , R 101g R is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , R 101d and R 101e and R 101fmay form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e and R 101d and R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the ring.

[0028] When the ionic polymer in the component (A) has an ammonium salt structure, such ammonium ions can be used.

[0029] It is preferable that the adhesive composition further contains a tackifying resin as component (B).

[0030] In this case, the component (B) is preferably at least one selected from a silicone resin, a (meth)acrylate resin, and a urethane resin.

[0031] Such a device can be in constant contact with the skin and can provide a stable electrical signal for a long period of time.

[0032] The component (B) preferably contains a diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a SiH group.

[0033] In this case, the component (B) further includes R x SiO (4-x) / 2 It is preferable that the silicone resin contains a silicone resin having a unit (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and a SiO2 unit.

[0034] Such a composition can be suitably used as a bioelectrode composition.

[0035] Furthermore, the component (C) preferably contains a polymeric compound having an ionic repeating unit.

[0036] In this case, it is preferable that the ionic repeating unit of the component (C) contains a repeating unit having a structure selected from the group consisting of the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide, as represented by the following general formula (2): [ka] (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 R each independently represents a single bond, or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have either an ester group or an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, R 7 In the formula, one or two of the hydrogen atoms may be substituted with a fluorine atom. Each of X1, X2, X3, X4, X6, and X7 is independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, and X5 is a single bond, an ether group, or an ester group. Y is an oxygen atom, -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may be bonded to form a ring. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 each satisfy 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0≦a7≦1.0, <a1+a2+a3+a4+a5+a6+a7≦1.0である。M +is an ion selected from an ammonium ion, a lithium ion, a sodium ion, a potassium ion, and a silver ion. Rf5, Rf6, and Rf7 are a fluorine atom, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom.

[0037] A bioelectrode composition containing a polymer compound having such a repeating unit can further improve the effects of the present invention.

[0038] Furthermore, it is preferable that the component (D) contains carbon powder and / or metal powder.

[0039] In this case, the carbon powder is preferably either or both of carbon black and carbon nanotubes.

[0040] The metal powder is preferably a metal powder selected from the group consisting of gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, and indium.

[0041] In this case, the metal powder is preferably silver powder.

[0042] This will result in even better electrical conductivity.

[0043] It is preferable that the component (E) further contains an organic solvent.

[0044] In this case, the coating properties of the bioelectrode composition are further improved.

[0045] The present invention also provides a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, wherein the biocontact layer is a cured product of the above-mentioned bioelectrode composition.

[0046] The bioelectrode of the present invention has excellent electrical conductivity and biocompatibility, is lightweight, and can be manufactured at low cost. Its electrical conductivity does not decrease significantly whether it is wet or dried, and it is a soft bioelectrode with excellent elasticity and adhesiveness.

[0047] In addition, the conductive substrate preferably contains one or more metals selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and conductive polymers.

[0048] In the bioelectrode of the present invention, such a conductive substrate can be particularly suitably used.

[0049] The present invention also provides a method for manufacturing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, in which the bioelectrode composition described above is applied to the conductive substrate and cured to form the biocontact layer.

[0050] The manufacturing method of the bioelectrode of the present invention makes it possible to easily manufacture a bioelectrode that is excellent in electrical conductivity and biocompatibility, lightweight, and can be manufactured at low cost, and that does not significantly decrease in electrical conductivity whether wetted or dried, and that is soft, stretchable, and adhesive.

[0051] In addition, it is preferable to use, as the conductive substrate, one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and conductive polymers.

[0052] In the method for producing a bioelectrode of the present invention, such a conductive substrate can be particularly preferably used. Effect of the Invention

[0053] As described above, the present invention provides a bioelectrode composition that is excellent in electrical conductivity and biocompatibility, lightweight, and can be manufactured at low cost, and that does not significantly decrease in electrical conductivity whether wetted with water or dried, and that can form a biocontact layer for a bioelectrode that is soft, stretchable, and adhesive; a bioelectrode in which a biocontact layer is formed from the bioelectrode composition; and a method for manufacturing the same. [Brief description of the drawings]

[0054] [Figure 1] FIG. 1 is a schematic cross-sectional view showing an example of a bioelectrode of the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of the bioelectrode of the present invention attached to a living body. [Diagram 3] FIG. 2 is a schematic diagram of a bioelectrode produced in an example of the present invention after printing. [Figure 4] FIG. 2 is a schematic diagram of one of the bioelectrodes produced in the examples of the present invention, cut out and with an adhesive layer and an electric wire attached. [Diagram 5] FIG. 2 is a diagram showing the locations where electrodes and a ground are attached to the human body when measuring a biosignal in an embodiment of the present invention. [Figure 6] 1 is an electrocardiogram waveform obtained using a bioelectrode according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0055] As described above, there has been a need to develop a bioelectrode composition capable of forming a biocontact layer for a bioelectrode that is excellent in electrical conductivity and biocompatibility, lightweight, can be manufactured at low cost, is soft, stretchable, and adhesive, can be attached to the skin for a long period of time to stably collect biosignals even when wetted with water such as during a bath or dried, and leaves no residue on the skin after being removed from the skin; a bioelectrode in which a biocontact layer is formed from the bioelectrode composition; and a method for manufacturing the same.

[0056] Sodium, potassium, and calcium ions are released from the skin surface in tandem with the heartbeat. Bioelectrodes need to convert the increase or decrease in the ions released from the skin into an electrical signal. To do this, materials with excellent ionic conductivity are required to transmit the increase or decrease in ions.

[0057] To stably obtain biosignals when attached to the skin, the bioelectrode film must be soft, stretchable, and adhesive. The keratin of the epidermis is regenerated daily, and old keratin (dirt) accumulates between the attached bioelectrode film and the skin. Since old keratin is easily peeled off from the epidermis, peeling off the bioelectrode makes it impossible to collect biosignals. For this reason, the adhesiveness of the bioelectrode must not decrease even when it is attached for a long period of time. On the other hand, if any residue remains on the skin after it is removed after being attached for a long period of time, it may cause rashes or rough skin.

[0058] Silicone adhesives are made by combining cross-linkable silicone with MQ resin. Silicone is inherently excellent in terms of peelability, but when combined with MQ resin, it exhibits adhesive properties.

[0059] In order to improve the adhesiveness of bioelectrodes, it is necessary to make the ionic polymer material itself adhesive. For this purpose, ladder-type T units (RSiO 3 / 2 ) would be effective, leading to the invention of the present invention.

[0060] The present inventors have developed a ladder-type T unit (RSiO 3 / 2 The present invention proposes a bioelectrode composition containing the silicone of formula (1) and a bioelectrode obtained by curing the composition.

[0061] When the acidity of the acid that forms the neutralized salt is high, the ions are strongly polarized, improving ionic conductivity. This is why lithium salts of bis(trifluoromethanesulfonyl)imide acid and tris(trifluoromethanesulfonyl)methide acid show high ionic conductivity in lithium-ion batteries. On the other hand, the higher the acid strength of the acid before it becomes a neutralized salt, the stronger the bioirritation of the salt. In other words, there is a trade-off between ionic conductivity and bioirritation. However, salts to be applied to bioelectrodes must have both high ionic conductivity and low bioirritation.

[0062] The larger the molecular weight of an ionic compound, the less permeable it is to the skin, and the less irritating it is to the skin. For this reason, a high molecular weight polymer type ionic compound is preferable. Therefore, the present inventors have polymerized this ionic compound into a form having a polymerizable double bond, copolymerized it with a monomer having an alkoxysilyl group, and converted the polymerized ionic polymer into a ladder type T unit (RSiO 3 / 2 ) silicone, it was discovered that a biological contact layer could be obtained that was soft, stretchy, adhesive, and highly sensitive to biological signals.

[0063] Furthermore, the inventors have discovered that by mixing this salt (silicone) with, for example, a silicone-based, acrylic-based, or urethane-based adhesive (resin), the adhesive can be more consistently in contact with the skin, and a stable electrical signal can be obtained for a long period of time.

[0064] As described above, since the ionic polymer itself has adhesiveness, it is not necessarily required to mix it with the adhesive.

[0065] When attaching or removing a bioelectrode, it is necessary to have a releasability. In this case, it may be mixed with a non-adhesive or slightly adhesive silicone-based, acrylic-based, or urethane-based resin. In this case, although the releasability is improved, the adhesion to the skin is reduced, and it may become impossible to collect a stable biosignal. Therefore, one of the aims of the present invention is to achieve both releasability and stability of the biosignal by using an ionic polymer with adhesiveness in order to obtain a stable biosignal even when mixed with a non-adhesive or slightly adhesive silicone-based, acrylic-based, or urethane-based resin.

[0066] That is, the present invention provides: A bioelectrode composition comprising: (A) A silicone bonded to an ionic polymer and having a structure (excluding a cage structure) containing a T unit represented by the following general formula (T1): (R 0 SiO 3 / 2 ) (T1) (In the formula, R 0 is a linking group to the ionic polymer. and In the bioelectrode composition, the ionic polymer is a polymer having a repeating unit having a structure selected from the group consisting of ammonium salts, lithium salts, sodium salts, potassium salts, and silver salts of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide.

[0067] The present invention will be described in detail below, but the present invention is not limited thereto.

[0068] <Bioelectrode composition> The bioelectrode composition of the present invention contains (A) a silicone bonded to an ionic polymer and having a structure (excluding a cage structure) containing a T unit, and preferably (B) an adhesive resin. Each component will be described in more detail below.

[0069] [(A) Silicone bonded to an ionic polymer and having a structure containing T units (excluding cage structures)] The component (A) in the present invention is a silicone that is bonded to an ionic polymer having a repeating unit having a structure selected from the group consisting of the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide, and that has a structure (excluding a cage structure) that includes a T unit represented by the following general formula (T1). (R 0 SiO 3 / 2 ) (T1) (In the formula, R 0 is a linking group to the ionic polymer.

[0070] The component (A) is, for example, a polymer formed by combining an ionic polymer and a ladder-type or random-type T unit (RSiO 3 / 2 ) silicone complex (bonded salt). Component (A) is obtained, for example, by a condensation reaction of a polymer compound (ionic intermediate polymer) obtained by copolymerizing a repeating unit having a structure selected from the group consisting of the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide, and a repeating unit having a trialkoxysilyl group.

[0071] The structures (repeating units) contained in the ionic polymer and the ionic intermediate polymer will be described below.

[0072] The repeating unit having a structure selected from the group consisting of ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide preferably has a structure represented by any of the following general formulas (1)-1 to (1)-4.

[0073] [ka] (In the formula, Rf1 and Rf2 are a hydrogen atom, a fluorine atom, an oxygen atom, a methyl group, or a trifluoromethyl group. When Rf1 and Rf2 are oxygen atoms, Rf1 and Rf2 are one oxygen atom bonding to one carbon atom to form a carbonyl group. Rf3 and Rf4 are a hydrogen atom, a fluorine atom, or a trifluoromethyl group. At least one of Rf1 to Rf4 is a fluorine atom or a trifluoromethyl group. Rf5, Rf6, and Rf7 are a fluorine atom or a linear or branched alkyl group having 1 to 4 carbon atoms and having at least one fluorine atom. m is an integer of 1 to 4. M + is an ion selected from ammonium ion, lithium ion, sodium ion, potassium ion, and silver ion.

[0074] (Repeating units a1 to a7) The repeating unit having a structure selected from the ammonium salt, lithium salt, sodium salt, potassium salt and silver salt of fluorosulfonic acid represented by general formula (1)-1 or (1)-2, sulfonimide represented by (1)-3 and N-carbonylsulfonamide represented by (1)-4 is preferably one or more selected from repeating units (2-1) to (2-7) (repeating units a1 to a7) represented by general formula (2) below.

[0075] [ka] (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 R each independently represents a single bond, or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have either an ester group or an ether group, or both. 7is a linear or branched alkylene group having 1 to 4 carbon atoms; R 7 In the formula, one or two of the hydrogen atoms may be substituted with a fluorine atom. Each of X1, X2, X3, X4, X6, and X7 is independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, and X5 is a single bond, an ether group, or an ester group. Y is an oxygen atom, -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may be bonded to form a ring. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 each satisfy 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0≦a7≦1.0, <a1+a2+a3+a4+a5+a6+a7≦1.0である。M + is an ion selected from an ammonium ion, a lithium ion, a sodium ion, a potassium ion, and a silver ion. Rf5, Rf6, and Rf7 are a fluorine atom, or a linear or branched alkyl group having 1 to 4 carbon atoms, and have at least one fluorine atom.

[0076] Among the repeating units a1 to a7 represented by the above general formula (2), specific examples of the fluorosulfonate monomer for obtaining the repeating units a1 to a5 are shown below.

[0077] [ka]

[0078] [ka]

[0079] [ka]

[0080] [ka]

[0081]

change

[0082]

change

[0083]

change

[0084]

change

[0085]

change

[0086]

change

[0087]

change

[0088]

change

[0089]

change

[0090]

change

[0091] [ka]

[0092] [ka]

[0093] [ka]

[0094] [ka]

[0095] [ka]

[0096] [ka]

[0097] [ka]

[0098] In the above general formula (2), specific examples of the sulfonimide salt monomer for obtaining the repeating unit a6 include those shown below.

[0099] [ka]

[0100] [ka]

[0101] [ka]

[0102] [ka]

[0103] [ka]

[0104] In the above general formula (2), specific examples of the N-carbonylsulfonamide salt monomer for obtaining the repeating unit a7 include those shown below.

[0105] [ka]

[0106] [ka] (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 , and R 13 As mentioned above.)

[0107] In addition, the component (A) contains, as an ammonium ion constituting an ammonium salt, particularly M in the repeating unit a (repeating units a1 to a7). + It is preferable that the ammonium ion (ammonium cation) is contained in the following general formula (5).

[0108] [ka] (In the formula, R 101d , R 101e , R 101f , R 101gR is a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , R 101d and R 101e and R 101f may form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e and R 101d and R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the ring.

[0109] Specific examples of the ammonium ion represented by the above general formula (5) include the following.

[0110] [ka]

[0111] [ka]

[0112] [ka]

[0113] [ka]

[0114] [ka]

[0115]

change

[0116]

change

[0117]

change

[0118]

change

[0119]

change

[0120]

change

[0121]

change

[0122]

change

[0123]

change

[0124]

change

[0125]

change

[0126] As the ammonium ion represented by the above general formula (5), a tertiary or quaternary ammonium ion is particularly preferred.

[0127] (Repeating unit b1) The ionic intermediate polymer in the present invention preferably contains, in addition to the repeating units a1 to a7, a repeating unit b1 having a trialkoxysilyl group represented by the following general formula (3).

[0128] [ka] (In the formula, R 20 is a hydrogen atom or a methyl group, X8 is a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, R 21 R is a single bond, a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms, or a phenylene group, which may contain an oxygen atom or a nitrogen atom. 22 are the same or different alkyl groups having 1 to 4 carbon atoms. b1 is 0 <b1<1.0である。)

[0129] Specific examples of monomers for obtaining the repeating unit b1 represented by formula (3) include those shown below.

[0130] [ka] (In the formula, R 20 is as mentioned above.)

[0131] (Repeating unit c) In the ionic polymer and ionic intermediate polymer in the component (A) of the bioelectrode composition of the present invention, in addition to the repeating units a1 to a7 and b1 described above, a repeating unit c having a glyme chain can be copolymerized to improve electrical conductivity. Specific examples of monomers for obtaining the repeating unit c having a glyme chain are shown below. By copolymerizing a repeating unit having a glyme chain, the movement of ions released from the skin in the dry electrode film can be promoted, and the sensitivity of the dry electrode can be increased.

[0132] [ka]

[0133] [ka]

[0134] [ka]

[0135] [ka] R is a hydrogen atom or a methyl group.

[0136] (Repeating unit d) In addition to the repeating units a1 to a7, b1, and c described above, the ionic polymer and ionic intermediate polymer in the component (A) of the bioelectrode composition of the present invention can also be copolymerized with a hydrophilic repeating unit d having a hydroxyl group, a carboxyl group, an ammonium salt, a betaine, an amide group, a pyrrolidone, a lactone ring, a lactam ring, a sultone ring, a sodium salt of sulfonic acid, or a potassium salt of sulfonic acid in order to improve electrical conductivity. Specific examples of monomers for obtaining the hydrophilic repeating unit d are listed below. By copolymerizing repeating units containing these hydrophilic groups, the sensitivity of the ions released from the skin can be increased, and the sensitivity of the dry electrode can be increased.

[0137] [ka]

[0138] [ka] R is a hydrogen atom or a methyl group.

[0139] (Repeating unit e) The ionic polymer and the ionic intermediate polymer in the component (A) in the bioelectrode composition of the present invention can have a repeating unit e that imparts adhesiveness. Specific examples of monomers for obtaining the repeating unit e include the following.

[0140] [ka]

[0141] [ka]

[0142] [ka]

[0143] [ka]

[0144] [ka]

[0145] (Repeating unit f) Furthermore, a crosslinkable repeating unit f can be copolymerized. Examples of the crosslinkable repeating unit include a repeating unit having an oxirane ring or an oxetane ring.

[0146] Specific examples of monomers for obtaining the repeating unit f having an oxirane ring or oxetane ring include those shown below.

[0147] [ka]

[0148] [ka] Here, R is a methyl group or a hydrogen atom.

[0149] (Repeating unit g) The ionic polymer and ionic intermediate polymer in the component (A) of the bioelectrode composition of the present invention can have a repeating unit g having silicon in addition to the repeating units selected from the above a1 to a7, b1, and c to f. Specifically, the following can be exemplified.

[0150] [ka] (n is a number between 0 and 100.)

[0151] [ka]

[0152] (Repeating unit h) The ionic polymer and ionic intermediate polymer in component (A) of the bioelectrode composition of the present invention can have a fluorine-containing repeating unit h in addition to the repeating units selected from the above a1 to a7 and b1 to g.

[0153] Specific examples of monomers for obtaining the fluorine-containing repeating unit h include the following.

[0154] [ka]

[0155] [ka]

[0156] [ka]

[0157] [ka]

[0158] [ka]

[0159] [ka]

[0160] [ka] Here, R is a hydrogen atom or a methyl group.

[0161] Ionic intermediate polymer One method for synthesizing an ionic intermediate polymer for obtaining component (A) is to heat-polymerize a desired monomer from among monomers that give the repeating units a1 to a7, b1, c, d, e, f, g, and h in an organic solvent with the addition of a radical polymerization initiator to obtain a polymer compound of a copolymer.

[0162] Examples of the organic solvent used during the polymerization include toluene, benzene, tetrahydrofuran, diethyl ether, dioxane, etc. Examples of the polymerization initiator include 2,2'-azobisisobutyronitrile (AIBN), 2,2'-azobis(2,4-dimethylvaleronitrile), dimethyl 2,2-azobis(2-methylpropionate), benzoyl peroxide, lauroyl peroxide, etc. The heating temperature is preferably 50 to 80°C, and the reaction time is preferably 2 to 100 hours, more preferably 5 to 20 hours.

[0163] Here, the ratios of the repeating units a1 to a7, b1, c, d, e, f, g, h in the ionic intermediate polymer are 0 ≦ a1 < 1.0, 0 ≦ a2 < 1.0, 0 ≦ a3 < 1.0, 0 ≦ a4 < 1.0, 0 ≦ a5 < 1.0, 0 ≦ a6 < 1.0, 0 ≦ a7 < 1.0, 0 < a1 + a2 + a3 + a4 + a5 + a6 + a7 < 1.0, 0 < b1 < 1.0, 0 ≦ c < 1.0, 0 ≦ d < 1.0, 0 ≦ e < 0.9, 0 ≦ f < 0.9, 0 ≦ g < 0.9, 0 ≦ h < 0.9, preferably 0 ≦ a1 ≦ 0.9, 0 ≦ a2 ≦ 0.9, 0 ≦ a3 ≦ 0.9, 0 ≦ a4 ≦ 0.9, 0 ≦ a5 ≦ 0.9, 0 ≦ a6 ≦ 0.9, 0 ≦ a7 ≦ 0.9, 0.01 ≦ a1 + a2 + a3 + a4 + a5 + a6 + a7 ≦ 0.99, 0.001 ≦ b1 ≦ 0.8, 0 ≦ c ≦ 0.8, 0 ≦ d ≦ 0.8, 0 ≦ e < 0.8, 0 ≦ f < 0.8, 0 ≦ g < 0.8, 0 ≦ h < 0.8, more preferably 0 ≦ a1 ≦ 0.8, 0 ≦ a2 ≦ 0.8, 0 ≦ a3 ≦ 0.8, 0 ≦ a4 ≦ 0.8, 0 ≦ a5 ≦ 0.8, 0 ≦ a6 ≦ 0.8, 0 ≦ a7 ≦ 0.8, 0.02 ≦ a1 + a2 + a3 + a4 + a5 + a6 + a7 ≦ 0.95, 0.01 ≦ b1 ≦ 0.7, 0 ≦ c ≦ 0.7, 0 ≦ d ≦ 0.5, 0 ≦ e < 0.3, 0 ≦ f < 0.7, 0 ≦ g < 0.7, 0 ≦ h < 0.7.

[0164] For example, a1+a2+a3+a4+a5+a6+a7+b1+c+d+e+f+g+h=1 means that in a polymer compound containing repeating units a1, a2, a3, a4, a5, a6, a7, b1, c, d, e, f, g, and h, the total amount of repeating units a1, a2, a3, a4, a5, a6, a7, b1, c, d, e, f, g, and h is 100 mol % based on the total amount of all repeating units. a1+a2+a3+a4+a5+a6+a7+b1+c+d+e+f+g+h<1 means that the total amount of repeating units a1, a2, a3, a4, a5, a6, a7, b1, c, d, e, f, g and h is less than 100 mol% based on the total amount of all repeating units, and the polymer has repeating units other than a1, a2, a3, a4, a5, a6, a7, b1, c, d, e, f, g and h.

[0165] The molecular weight of the ionic intermediate polymer is preferably 500 or more as weight average molecular weight, more preferably 1,000 or more and 1,000,000 or less, and even more preferably 2,000 or more and 500,000 or less. In addition, if the amount of ionic monomer (residual monomer) that is not incorporated into the ionic intermediate polymer after polymerization is small, there is no risk of it penetrating into the skin and causing allergies in a biocompatibility test, so it is preferable to reduce the amount of the residual monomer. The amount of the residual monomer is preferably 10 parts by mass or less relative to 100 parts by mass of the entire ionic intermediate polymer. In addition, the ionic intermediate polymer may be used alone or may be used in a mixture of two or more types having different molecular weights, dispersities, and polymerized monomers.

[0166] (A) Silicone bonded to an ionic polymer and having a structure containing T units (excluding cage structures) The component (A) in the present invention can be obtained as a condensation reaction product of the above-mentioned ionic intermediate polymer. In the case of an ionic intermediate polymer in which a repeating unit having an alkoxysilyl group as shown in the following general formula (3) is copolymerized in addition to the repeating unit as shown in the above general formula (2), the condensation reaction product is a silicone having a structure containing a ladder-type or random-type T unit bonded to the ionic polymer and having a repeating unit as shown in the following general formula (4).

[0167] [ka] (In the formula, R 20 is a hydrogen atom or a methyl group, X8 is a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, R 21 R is a single bond, a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms, or a phenylene group, which may contain an oxygen atom or a nitrogen atom. 22 are the same or different alkyl groups having 1 to 4 carbon atoms. b1 is 0 <b1<1.0である。)

[0168] [ka] (In the formula, R 20 , X8, R 21 , and b1 are as described above.)

[0169] The molecular weight is increased by hydrolysis of the alkoxysilyl groups of the ionic intermediate polymer in which the repeating unit represented by the general formula (3) is copolymerized to form a ladder-type or random-type silicone.

[0170] Examples of silicones with T units include ladder type, random type, and cage type. Cage type silicone copolymer ionic polymers are exemplified in JP-A Nos. 2018-110845, 2018-99504, and 2019-011454, but no effect of improving adhesion is observed. However, by copolymerizing ladder type or random type silicone, adhesion is improved. This is thought to be an effect due to the structure of ladder type or random type silicone.

[0171] Monomers having cage-type T units are described in the specific examples of repeating unit g above. Cage-type T unit silicone is formed during monomer synthesis. On the other hand, T unit silicone formed by condensation reaction after polymerization of trialkoxysilane-containing monomer is ladder type or random type, not cage type.

[0172] The silicone in component (A) is not particularly limited as long as it has a structure containing T units other than a cage structure, such as a ladder type or random type structure, and it is optional for it to have a cage structure in addition to these structures.

[0173] The polymer (component (A)) after the condensation reaction can be represented by the following general formula (2)'.

[0174] [ka] (In the formula, R 1 ~R 14 , R 20 , R 21 , X1~X 8、 Y, m, M + , Rf5 to Rf7, a1 to a7, and b1 are as described above.)

[0175] When carrying out the condensation reaction in synthesizing the component (A), it is possible to co-condense with another alkoxysilane. The repeating unit b2 obtained from the other alkoxysilane can be shown below.

[0176] [ka]

[0177] [ka]

[0178] [ka]

[0179] [ka]

[0180] As the repeating unit b2 obtained from another alkoxysilane, a sulfonate silsesquioxane can also be copolymerized. The sulfonate silsesquioxane preferably has a repeating unit represented by the following general formula:

[0181] [ka] (In the formula, R 30 is a linear, branched or cyclic alkylene group having 1 to 20 carbon atoms, which may have an aromatic group, an ether group, an ester group or a fluorine atom, or is an arylene group having 6 to 10 carbon atoms. Rf1' to Rf4' are hydrogen atoms, fluorine atoms or trifluoromethyl groups, Rf1' to Rf4' each having one or more fluorine atoms, and Rf3' and Rf4' may be bonded to each other with an oxygen atom to form a double bond. M + is a lithium ion, a sodium ion, a potassium ion, or a silver ion.)

[0182] Specific examples of the repeating unit of the sulfonate silsesquioxane represented by the above general formula are shown below.

[0183] [ka]

[0184] [ka]

[0185] [ka]

[0186] [ka]

[0187] [ka]

[0188] [ka]

[0189] [ka]

[0190] [ka]

[0191] [ka]

[0192] [ka]

[0193] [ka]

[0194] As the repeating unit b2 obtained from another alkoxysilane, a sulfonimide salt silsesquioxane can also be copolymerized. The sulfonimide salt silsesquioxane preferably has a repeating unit represented by the following general formula:

[0195] [ka] (In the formula, R 31 is a linear, branched or cyclic alkylene group having 2 to 20 carbon atoms, which may have an aromatic group, an ether group or an ester group, or is an arylene group having 6 to 10 carbon atoms. Rf' is a linear, branched or cyclic alkyl group having 1 to 4 carbon atoms, which has at least one fluorine atom. M +is a lithium ion, a sodium ion, a potassium ion, or a silver ion.)

[0196] Specific examples of the repeating unit of the sulfonimide salt silsesquioxane represented by the above general formula include those shown below.

[0197] [ka]

[0198] [ka]

[0199] [ka]

[0200] As the repeating unit b2 obtained from another alkoxysilane, a silsesquioxane bonded to an N-carbonylsulfonamide salt can also be copolymerized. The silsesquioxane bonded to an N-carbonylsulfonamide salt preferably has a repeating unit represented by the following general formula:

[0201] [ka] (In the formula, R 32 is a linear, branched or cyclic alkylene group having 2 to 20 carbon atoms, which may have an aromatic group, an ether group or an ester group, or is an arylene group having 6 to 10 carbon atoms. Rf' is a linear, branched or cyclic alkyl group having 1 to 4 carbon atoms, which has at least one fluorine atom. M + is a lithium ion, a sodium ion, a potassium ion, or a silver ion.)

[0202] Specific examples of the repeating unit of silsesquioxane bonded to the N-carbonylsulfonamide salt represented by the above general formula include those shown below.

[0203] [ka]

[0204] [ka]

[0205] [ka] Here, M + is as mentioned above.

[0206] In the component (A) of the bioelectrode composition of the present invention, in addition to the above repeating units, a repeating unit of silsesquioxane having a glyme chain can be copolymerized as the repeating unit b2 obtained from another alkoxysilane in order to improve the electrical conductivity. Specific examples include the following.

[0207] [ka]

[0208] [ka] (In the formula, 0≦m≦20, 0≦n≦20, and 1≦m+n≦20.)

[0209] By combining silicone Q units as well as T units in component (A), the adhesiveness is further improved, and a stable biosignal with less baseline drift and noise can be obtained. By combining highly polarizable T units such as cyano and nitro groups, ionic T units, and T units with glyme chains in component (A), the ionic conductivity can be improved.

[0210] Here, the ratios of b1 and b2 are such that 0 < b1 / (b1 + b2) ≤ 1.0, 0 ≤ b2 / (b1 + b2) < 1.0, preferably 0.1 ≤ b1 / (b1 + b2) ≤ 1.0, 0 ≤ b2 / (b1 + b2) ≤ 0.8, and more preferably 0.3 ≤ b1 / (b1 + b2) ≤ 1.0, 0 ≤ b2 / (b1 + b2) ≤ 0.7.

[0211] In the biological electrode composition of the present invention, the blending amount of the component (A) is preferably 0.1 to 300 parts by mass, and more preferably 1 to 200 parts by mass, based on 100 parts by mass of the component (B) described below. Also, the component (A) may be used alone or in combination of two or more.

[0212] [(B) Adhesive resin] The (B) adhesive resin blended in the biological electrode composition of the present invention is a component that is compatible with the complex (salt) of the above-mentioned component (A) to prevent elution of the salt, holds conductivity improvers such as metal powder, carbon powder, silicon powder, lithium titanate powder, etc., and further improves adhesiveness. When the component (A) has sufficient adhesiveness, the (B) adhesive resin is not necessarily required. The resin of the component (B) may be any resin other than the above-mentioned component (A), and is preferably either a thermosetting resin or a photocurable resin, or both, and particularly preferably one or more selected from silicone-based, acrylic-based, and urethane-based resins.

[0213] Examples of the adhesive silicone-based resin include those of the addition reaction curing type or the radical crosslinking reaction curing type. Examples of the addition reaction curing type include those described in JP-A-2015-193803, which contain an alkenyl group-containing diorganosiloxane, R3SiO 0.5 and an MQ resin having SiO2 units, an organohydrogenpolysiloxane having a plurality of SiH groups, a platinum catalyst, an addition reaction control agent, and an organic solvent. Also, examples of the radical crosslinking reaction curing type include those described in JP-A-2015-193803, which may or may not have an alkenyl group-containing diorganopolysiloxane, R3SiO 0.5and those containing an MQ resin having SiO2 units, an organic peroxide, and an organic solvent, where R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms.

[0214] It is also possible to use a polysiloxane-resin integrated compound formed by condensing polysiloxane with silanols at the polymer end or side chain with MQ resin. MQ resin contains a lot of silanols, so adding this improves adhesive strength, but since it is not crosslinkable, it is not molecularly bonded to the polysiloxane. By integrating polysiloxane and resin as described above, adhesive strength can be increased.

[0215] In addition, modified siloxanes having a group selected from amino groups, oxirane groups, oxetane groups, polyether groups, hydroxy groups, carboxyl groups, mercapto groups, methacryl groups, acrylic groups, phenol groups, silanol groups, carboxylic anhydride groups, aryl groups, aralkyl groups, amide groups, ester groups, and lactone rings can be added to silicone resins. By adding modified siloxanes, the dispersibility of component (A) in the silicone resin is improved. The modified siloxanes may be modified at one end, both ends, or the side chains of the siloxane.

[0216] The adhesive acrylic resin may be, for example, one having a hydrophilic (meth)acrylic acid ester or a long-chain hydrophobic (meth)acrylic acid ester as a repeating unit, as described in JP 2016-011338 A. In some cases, a (meth)acrylic acid ester having a functional group or a (meth)acrylic acid ester having a siloxane bond may be copolymerized.

[0217] As the adhesive urethane-based resin, for example, one having a urethane bond and a polyether or polyester bond, a polycarbonate bond, or a siloxane bond, as described in JP 2016-065238 A, can be used.

[0218] In addition, in order to prevent the decrease in conductivity due to the detachment of the (A) component from the biocontact layer, in the bioelectrode composition of the present invention, it is preferable that the resin of the (B) component has high compatibility with the above-mentioned (A) component. In addition, in order to prevent the peeling of the biocontact layer from the conductive substrate, it is preferable that the resin of the (B) component has high adhesion to the conductive substrate in the bioelectrode composition of the present invention. In order to make the resin of the (B) component highly compatible with the conductive substrate and salt, it is effective to use a resin with high polarity. Examples of such resins include resins having one or more selected from ether bonds, ester bonds, amide bonds, imide bonds, urethane bonds, thiourethane bonds, and thiol groups, or polyacrylic resins, polyamide resins, polyimide resins, polyurethane resins, and polythiourethane resins. On the other hand, since the biocontact layer contacts the living body, it is easily affected by sweat from the living body. Therefore, in the bioelectrode composition of the present invention, it is preferable that the (B) resin has high water repellency and is not easily hydrolyzed. In order to make the resin of the (B) component highly water repellent and not easily hydrolyzed, it is effective to use a resin containing silicon.

[0219] Silicon-atom-containing polyacrylic resins include polymers having silicone in the main chain and polymers having silicon atoms in the side chain, and both can be used suitably. As the polymer having silicone in the main chain, siloxane or silsesquioxane having a (meth)acrylpropyl group can be used. In this case, the (meth)acryl portion can be polymerized and cured by adding a photoradical generator.

[0220] Suitable examples of polyamide resins containing silicon atoms include polyamide silicone resins described in JP 2011-079946 A and U.S. Patent No. 5,981,680 A. Such polyamide silicone resins can be synthesized by combining, for example, a silicone having amino groups at both ends or a non-silicone compound having amino groups at both ends with a non-silicone having carboxyl groups at both ends or a silicone having carboxyl groups at both ends.

[0221] Alternatively, polyamic acid obtained by reacting a carboxylic anhydride with an amine before cyclization may be used. An epoxy or oxetane crosslinking agent may be used to crosslink the carboxyl groups of the polyamic acid, or the carboxyl groups may be esterified with hydroxyethyl (meth)acrylate to perform photoradical crosslinking of the (meth)acrylate portion.

[0222] As the polyimide resin containing silicon atoms, for example, the polyimide silicone resin described in JP-A-2002-332305 can be suitably used. Polyimide resins have a very high viscosity, but the viscosity can be reduced by blending a (meth)acrylic monomer as a solvent and a crosslinking agent.

[0223] Examples of polyurethane resins containing silicon atoms include polyurethane silicone resins. In such polyurethane silicone resins, crosslinking by urethane bonds can be performed by blending and heating a compound having isocyanate groups at both ends and a compound having hydroxyl groups at the ends. In this case, it is necessary to contain silicon atoms (siloxane bonds) in either or both of the compound having isocyanate groups at both ends and the compound having hydroxyl groups at the ends. Alternatively, as described in JP 2005-320418 A, a urethane (meth)acrylate monomer can be blended with polysiloxane to perform photocrosslinking. In addition, a polymer having both siloxane bonds and urethane bonds and a (meth)acrylate group at the end can also be photocrosslinked. In particular, materials having silicone chains attached to side chains and polyurethane main chains described in JP 2018-123304 A and JP 2019-70109 A are preferred because they have high strength and high elasticity.

[0224] The polythiourethane resin containing silicon atoms can be obtained by reacting a compound having a thiol group with a compound having an isocyanate group, and any one of them may contain a silicon atom. In addition, if the compound has a (meth)acrylate group at the end, it can be photocured.

[0225] In the silicone resin, the above-mentioned diorganosiloxane having an alkenyl group, RSiO 0.5 In addition to MQ resins having SiO2 units and organohydrogenpolysiloxanes having multiple SiH groups, the compatibility with the above-mentioned salts is improved by adding modified siloxanes having groups selected from amino groups, oxirane groups, oxetane groups, polyether groups, hydroxyl groups, carboxyl groups, mercapto groups, methacryl groups, acrylic groups, phenol groups, silanol groups, carboxylic anhydride groups, aryl groups, aralkyl groups, amide groups, ester groups, and lactone rings.

[0226] Diorganosiloxanes having alkenyl groups and organohydrogenpolysiloxanes having multiple SiH groups can be crosslinked by an addition reaction in the presence of a platinum catalyst.

[0227] Examples of platinum catalysts include platinum catalysts such as chloroplatinic acid, alcohol solutions of chloroplatinic acid, reaction products of chloroplatinic acid and alcohol, reaction products of chloroplatinic acid and olefin compounds, reaction products of chloroplatinic acid and vinyl group-containing siloxane, platinum-olefin complexes, platinum-vinyl group-containing siloxane complexes, platinum group metal catalysts such as rhodium complexes and ruthenium complexes, etc. Furthermore, these catalysts may be used in the form of a solution or dispersion in an alcohol-based, hydrocarbon-based, or siloxane-based solvent.

[0228] The amount of the platinum catalyst added is preferably within a range of 5 to 2,000 ppm, and particularly preferably 10 to 500 ppm, per 100 parts by mass of the resin of component (B).

[0229] In the bioelectrode composition of the present invention, the blending amount of the (B) component is preferably 0 to 2000 parts by mass, more preferably 10 to 1000 parts by mass, per 100 parts by mass of the complex of the ionic polymer and the T unit silicone ((A) component). The (B) component may be used alone or in combination of two or more kinds.

[0230] When an addition-curing silicone resin is used, an addition reaction inhibitor may be added as a quencher to prevent the platinum catalyst from acting in the solution and in a low-temperature environment before heat curing after coating formation. Specific examples include 3-methyl-1-butyn-3-ol, 3-methyl-1-pentyn-3-ol, 3,5-dimethyl-1-hexyn-3-ol, 1-ethynylcyclohexanol, 3-methyl-3-trimethylsiloxy-1-butyne, 3-methyl-3-trimethylsiloxy-1-pentyne, 3,5-dimethyl-3-trimethylsiloxy-1-hexyne, 1-ethynyl-1-trimethylsiloxycyclohexane, bis(2,2-dimethyl-3-butynoxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,1,3,3-tetramethyl-1,3-divinyldisiloxane.

[0231] The amount of the addition reaction inhibitor added is preferably within the range of 0 to 10 parts by mass, and particularly preferably 0.05 to 3 parts by mass, per 100 parts by mass of the resin of component (B).

[0232] When component (B) has a radically crosslinkable double bond, it is effective to add a radical generator. Radical generators include photoradical generators and thermal radical generators.

[0233] Examples of photoradical generators include acetophenone, 4,4'-dimethoxybenzyl, benzil, benzoin, benzophenone, 2-benzoylbenzoic acid, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin butyl ether, benzoin isobutyl ether, 4-benzoylbenzoic acid, 2,2'-bis(2-chlorophenyl)-4,4',5,5'-tetraphenyl-1,2'-biimidazole, 2-benzoylbenzoic acid methyl ester, 2-(1,3-benzodioxol-5-yl)-4,6-bis(trichloromethyl)-1,3,5-triazine, 2-benzoylbenzoic acid methyl ester ... Examples of suitable acetophenones include 2-(dimethylamino)-4'-morpholinobutyrophenone, 4,4'-dichlorobenzophenone, 2,2-diethoxyacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,4-diethylthioxanthen-9-one, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide (BAPO), 1,4-dibenzoylbenzene, 2-ethylanthraquinone, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylpropiophenone, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, 2-isonitrosopropiophenone, and 2-phenyl-2-(p-toluenesulfonyloxy)acetophenone.

[0234] It can also be cured by adding a thermally decomposable radical generator. Examples of thermal radical generators include 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 2,2'-azobis(methylpropionamidine) hydrochloride, 2,2'-azobis[2-(2-imidazolin-2-yl)propane]hydrochloride, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(cyclohexane-1-carbonitrile), 1[(1-cyano-1-methylethyl)azo]formamide, 2,2'-azobis[2-methyl-N-(2-hydroxyethyl )propionamide], 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 2,2'-azobis(N-butyl-2-methylpropionamide), dimethyl-2,2'-azobis(isobutyrate), 4,4'-azobis(4-cyanopentanoic acid), dimethyl-2,2'-azobis(2-methylpropionate), benzoyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide, di-tert-butyl peroxide, di-tert-amyl peroxide, di-n-butyl peroxide, dicumyl peroxide, and the like.

[0235] The amount of the radical generator added is preferably within a range of 0.1 to 50 parts by mass per 100 parts by mass of the resin of the component (B).

[0236] Among these, the resin of component (B) is more preferably one containing a diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a SiH group, and further preferably R x SiO (4-x) / 2 Particularly preferred are those containing a silicone resin having a unit (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and a SiO2 unit.

[0237] As described later, the biocontact layer is a cured product of the bioelectrode composition. By curing, the adhesion of the biocontact layer to both the skin and the conductive substrate is improved. The curing method is not particularly limited, and a general method can be used, for example, heat and / or light, or a crosslinking reaction using an acid or base catalyst. The crosslinking reaction can be carried out by appropriately selecting a method described in, for example, Crosslinking Reaction Handbook, Nakayama Hiroharu, Maruzen Publishing (2013), Chapter 2, p. 51 to p. 371.

[0238] [(C) Blended ionic polymer] In addition to the component (A), an ionic polymer (blended ionic polymer) can be added to the bioelectrode composition of the present invention. The repeating units of the blended ionic polymer can be those explained in the component (A), particularly those represented by the general formula (2). The amount of the blended ionic polymer added is preferably in the range of 0.1 to 100 parts by mass per 100 parts by mass of the resin of the component (B).

[0239] [(D) Conductive powder] [Metal powder] In order to increase the electronic conductivity, the bioelectrode composition of the present invention may contain, as component (D), a metal powder selected from gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, and indium. The amount of metal powder added is preferably within the range of 1 to 50 parts by mass per 100 parts by mass of the resin of component (B).

[0240] As the type of metal powder, gold, silver, and platinum are preferred from the viewpoint of electrical conductivity, and silver, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, and chromium are preferred from the viewpoint of cost. From the viewpoint of biocompatibility, noble metals are preferred, and from these viewpoints overall, silver is the most preferred.

[0241] The shape of the metal powder can be spherical, disk-like, flake-like, or needle-like, but the addition of flake-like powder is the most conductive and is preferred. The size of the metal powder is 100 μm or less, and the tap density is 5 g / cm. 3 Below, the specific surface area is 0.5m 2 Flakes with a relatively low density and large specific surface area of ​​100 / g or more are preferred.

[0242] [Carbon powder] A carbon material (carbon powder) can be added as a conductivity improver. Examples of the carbon material include carbon black, graphite, carbon nanotubes, carbon fibers, graphene, etc. The carbon nanotubes may be either single-walled or multi-walled, and the surface may be modified with an organic group. The amount of the carbon material added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin of component (B).

[0243] [Silicon powder] Silicon powder can be added to the bioelectrode composition of the present invention in order to increase the sensitivity of ion reception. Examples of silicon powder include powders made of silicon, silicon monoxide, and silicon carbide. The particle size of the powder is preferably smaller than 100 μm, and more preferably 1 μm or less. Since finer particles have a larger surface area, they can receive more ions, resulting in a highly sensitive bioelectrode. The amount of silicon powder added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin of component (B).

[0244] [Lithium titanate powder] Lithium titanate powder can be added to the bioelectrode composition of the present invention in order to increase the sensitivity of ion reception. Lithium titanate powder includes Li2TiO3, LiTiO2, and Li4Ti5O with a spinel structure. 12The molecular formula of the lithium titanate powder is as follows, and a spinel structure is preferable. Lithium titanate particles composited with carbon can also be used. The particle size of the powder is preferably smaller than 100 μm, more preferably 1 μm or less. Since finer particles have a larger surface area, they can receive more ions, resulting in a highly sensitive bioelectrode. These may be composite powders with carbon. The amount of lithium titanate powder added is preferably in the range of 1 to 50 parts by mass per 100 parts by mass of the resin of component (B).

[0245] [(E) Organic solvent] In addition, an organic solvent can be added as component (E) to the bioelectrode composition of the present invention. Specific examples of the organic solvent include toluene, xylene, cumene, 1,2,3-trimethylbenzene, 1,2,4-trimethylbenzene, 1,3,5-trimethylbenzene, styrene, α-methylstyrene, butylbenzene, sec-butylbenzene, isobutylbenzene, cymene, diethylbenzene, 2-ethyl-p-xylene, 2-propyltoluene, 3-propyltoluene, 4-propyltoluene, 1,2,3,5-tetramethyltoluene, 1,2,4,5-tetramethyltoluene, and tetrahydrofuran. naphthalene, 4-phenyl-1-butene, tert-amylbenzene, amylbenzene, 2-tert-butyltoluene, 3-tert-butyltoluene, 4-tert-butyltoluene, 5-isopropyl-m-xylene, 3-methylethylbenzene, tert-butyl-3-ethylbenzene, 4-tert-butyl-o-xylene, 5-tert-butyl-m-xylene, tert-butyl-p-xylene, 1,2-diisopropylbenzene, 1,3-diisopropylbenzene, 1,4-diisopropylbenzene, Aromatic hydrocarbon solvents such as isopropylbenzene, dipropylbenzene, pentamethylbenzene, hexamethylbenzene, hexylbenzene, and 1,3,5-triethylbenzene, n-heptane, isoheptane, 3-methylhexane, 2,3-dimethylpentane, 3-ethylpentane, 1,6-heptadiene, 5-methyl-1-hexyne, norbornane, norbornene, dicyclopentadiene, 1-methyl-1,4-cyclohexadiene, 1-heptyne, 2-heptyne, cycloheptane, and cyclohexene. butene, 1,3-dimethylcyclopentane, ethylcyclopentane, methylcyclohexane, 1-methyl-1-cyclohexene, 3-methyl-1-cyclohexene, methylenecyclohexane, 4-methyl-1-cyclohexene, 2-methyl-1-hexene, 2-methyl-2-hexene, 1-heptene, 2-heptene, 3-heptene, n-octane, 2,2-dimethylhexane, 2,3-dimethylhexane, 2,4-dimethylhexane, 2,5-dimethylhexane, 3,3-dimethylhexane, 3,4-Dimethylhexane, 3-ethyl-2-methylpentane, 3-ethyl-3-methylpentane, 2-methylheptane, 3-methylheptane, 4-methylheptane, 2,2,3-trimethylpentane, 2,2,4-trimethylpentane, cyclooctane, cyclooctene, 1,2-dimethylcyclohexane, 1,3-dimethylcyclohexane, 1,4-dimethylcyclohexane, ethylcyclohexane, vinylcyclohexane, isopropylcyclopentane, 2,2-dimethyl-3-hexene, 2,4-dimethyl-1-hexene, 2,5-dimethyl-1- Hexene, 2,5-dimethyl-2-hexene, 3,3-dimethyl-1-hexene, 3,4-dimethyl-1-hexene, 4,4-dimethyl-1-hexene, 2-ethyl-1-hexene, 2-methyl-1-heptene, 1-octene, 2-octene, 3-octene, 4-octene, 1,7-octadiene, 1-octyne, 2-octyne, 3-octyne, 4-octyne, n-nonane, 2,3-dimethylheptane, 2,4-dimethylheptane, 2,5-dimethylheptane, 3,3-dimethylheptane, 3,4-dimethylheptane, 3,5-dimethylheptane, 4-ethylhexene, ethylheptane, 2-methyloctane, 3-methyloctane, 4-methyloctane, 2,2,4,4-tetramethylpentane, 2,2,4-trimethylhexane, 2,2,5-trimethylhexane, 2,2-dimethyl-3-heptene, 2,3-dimethyl-3-heptene, 2,4-dimethyl-1-heptene, 2,6-dimethyl-1-heptene, 2,6-dimethyl-3-heptene, 3,5-dimethyl-3-heptene, 2,4,4-trimethyl-1-hexene, 3,5,5-trimethyl-1-hexene, 1-ethyl-2-methylcyclohexane, 1-ethyl-3 -Methylcyclohexane, 1-ethyl-4-methylcyclohexane, propylcyclohexane, isopropylcyclohexane, 1,1,3-trimethylcyclohexane, 1,1,4-trimethylcyclohexane, 1,2,3-trimethylcyclohexane, 1,2,4-trimethylcyclohexane, 1,3,5-trimethylcyclohexane, allylcyclohexane, hydrindane, 1,8-nonadiene, 1-nonyne, 2-nonyne, 3-nonyne, 4-nonyne, 1-nonene, 2-nonene, 3-nonene, 4-nonene, n-decane, 3,3-dimethyloctane, 3,5-dimethyloctane, 4,4-dimethyloctane, 3-ethyl-3-methylheptane, 2-methylnonane, 3-methylnonane, 4-methylnonane, tert-butylcyclohexane, butylcyclohexane, isobutylcyclohexane, 4-isopropyl-1-methylcyclohexane, pentylcyclopentane, 1,1,3,5-tetramethylcyclohexane, cyclododecane, 1-decene, 2-decene, 3-decene, 4-decene, 5-decene, 1,9-decadiene, decahydronaphthalene, 1-decene, 2-decene, 3-decene, 4-decene, 5-decene, 1, 5,9-Decatriene, 2,6-dimethyl-2,4,6-octatriene, limonene, myrcene, 1,2,3,4,5-pentamethylcyclopentadiene, α-phellandrene, pinene, terpinene, tetrahydrodicyclopentadiene, 5,6-dihydrodicyclopentadiene, 1,4-decadiyne, 1,5-decadiyne, 1,9-decadiyne, 2,8-decadiyne, 4,6-decadiyne, n-undecane, amylcyclohexane, 1-undecene, 1,10-undecadiene, 1-undecyne, 3-undecyne, 5-undecyne, tricyclo[6.2.1.0, 2,7]Undec-4-ene, n-dodecane, n-tridecane, n-pentadecane, n-hexadecane, 2-methylundecane, 3-methylundecane, 4-methylundecane, 5-methylundecane, 2,2,4,6,6-pentamethylheptane, 1,3-dimethyladamantane, 1-ethyladamantane, 1,5,9-cyclododecatriene, 1,2,Aliphatic hydrocarbon solvents such as 4-trivinylcyclohexane and isoparaffin; ketone solvents such as cyclohexanone, cyclopentanone, 2-octanone, 2-nonanone, 2-heptanone, 3-heptanone, 4-heptanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methylcyclohexanone, and methyl n-pentyl ketone; alcohol solvents such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, and diethylene glycol monoheptyl ether. Examples of the solvent include ether solvents such as ethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, diisopropyl ether, diisobutyl ether, diisopentyl ether, di-n-pentyl ether, methylcyclopentyl ether, methylcyclohexyl ether, di-n-butyl ether, di-sec-butyl ether, diisopentyl ether, di-sec-pentyl ether, di-tert-amyl ether, di-n-hexyl ether, and anisole; ester solvents such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate; lactone solvents such as γ-butyrolactone; and water.

[0246] The amount of the organic solvent added is preferably within a range of 10 to 50,000 parts by mass per 100 parts by mass of the resin of the component (B).

[0247] [(F) Other additives] The bioelectrode composition of the present invention can be mixed with a platinum catalyst, an addition reaction control agent, a radical generator, a crosslinking agent, a crosslinking catalyst, an ionic additive, and further with silica particles, polyether silicone, and polyglycerin silicone, as well as the platinum catalyst, an addition reaction control agent, and a radical generator, as described in the (B) component section. Silica particles have a hydrophilic surface, and are compatible with hydrophilic ionic polymers, polyether silicones, and polyglycerin silicones, and can improve the dispersibility of ionic polymers, polyether silicones, and polyglycerin silicones in hydrophobic silicone adhesives. Silica particles can be used preferably in either dry or wet processes.

[0248] [Crosslinking agent] An epoxy-based crosslinking agent can be added to the bioelectrode composition of the present invention. In this case, the crosslinking agent is a compound having multiple epoxy groups or oxetane groups in one molecule. The amount of the crosslinking agent to be added is 1 to 30 parts by mass per 100 parts by mass of the resin of component (B).

[0249] [Crosslinking catalyst] A catalyst for crosslinking epoxy groups or oxetane groups can also be added to the bioelectrode composition of the present invention. In this case, the catalysts described in paragraphs 0027 to 0029 of JP-A-2019-503406 can be used. The amount of the catalyst added is 0.01 to 10 parts by mass per 100 parts by mass of the resin of component (B).

[0250] [Ionic additives] The bioelectrode composition of the present invention can be added with an ionic additive to increase ionic conductivity. In consideration of biocompatibility, sodium chloride, potassium chloride, calcium chloride, magnesium chloride, saccharin sodium salt, acesulfame potassium, sodium carboxylate, potassium carboxylate, calcium carboxylate, sodium sulfonate, potassium sulfonate, calcium sulfonate, sodium phosphate, potassium phosphate, calcium phosphate, magnesium phosphate, betaine, and salts disclosed in JP-A-2018-44147, JP-A-2018-59050, JP-A-2018-59052, and JP-A-2018-130534 can be mentioned.

[0251] [Silicone compounds with polyglycerin structure] In the bioelectrode composition of the present invention, a silicone compound having a polyglycerin structure can be added in order to improve the moisture retention of the membrane and improve the sensitivity and ion conductivity of ions released from the skin. The amount of the silicone compound having a polyglycerin structure is preferably 0.01 to 100 parts by mass, more preferably 0.5 to 60 parts by mass, per 100 parts by mass of the total of the (A) component and the (B) component. The silicone compound having a polyglycerin structure may be used alone or in a mixture of two or more types.

[0252] The silicone compound having a polyglycerin structure is preferably one represented by the following general formulas (4)' and (5)'.

[0253] [ka] (In formulas (4)' and (5)', R 1 are each independent and may be the same or different, each independently represent a hydrogen atom, a linear or branched alkyl group having 1 to 50 carbon atoms, or a phenyl group, each independently represent a silicone chain represented by the general formula (6)' ... 2R′ is a group having a polyglycerin group structure represented by formula (4)′-1 or formula (4)′-2, 3 ' are each independent and may be the same or different, 1 ' group or the R 2 ' group, R 4 ' are each independent and may be the same or different, 1 ' group, the R 2 R is a ' group or an oxygen atom. 4 If ' is an oxygen atom, R 4 The a' groups may be bonded to form a single ether group to form a ring together with the silicon atom. a' may be the same or different and is 0 to 100, b' is 0 to 100, and a'+b' is 0 to 200. However, when b' is 0, R 3 At least one of the R 2 In formulae (4)'-1, (4)'-2 and (5)', R 5 ' is an alkylene group having 2 to 10 carbon atoms or an aralkylene group having 7 to 10 carbon atoms; R 6 'R 7 ' is an alkylene group having 2 to 6 carbon atoms, and R 7 ' may be an ether bond, c' is 0 to 20, and d' is 1 to 20.

[0254] Examples of such silicone compounds having a polyglycerin structure include the following.

[0255] [ka]

[0256] [ka]

[0257] [ka]

[0258] [ka]

[0259] [ka]

[0260] [ka]

[0261] [ka]

[0262] [ka]

[0263] [ka]

[0264] [ka] (wherein a', b', c' and d' are as defined above).

[0265] A bioelectrode composition containing a silicone compound having such a polyglycerin structure can exhibit better moisturizing properties, and as a result, can form a biocontact layer that can exhibit better sensitivity to ions released from the skin.

[0266] As described above, the bioelectrode composition of the present invention is a bioelectrode composition capable of forming a biocontact layer for a bioelectrode that has high adhesion, has sufficient adhesion even when peeled off from the skin and reattached, can efficiently transmit electrical signals from the skin to a device (i.e., has excellent conductivity), is free from the risk of allergies even when worn on the skin for a long period of time (i.e., has excellent biocompatibility), is lightweight, can be manufactured at low cost, and does not significantly decrease in conductivity even when wet or dried. In addition, the conductivity can be further improved by adding a conductive powder (carbon powder, metal powder), and a bioelectrode with particularly high adhesion and high elasticity can be manufactured by combining it with a resin having adhesiveness and elasticity. Furthermore, the elasticity and adhesiveness to the skin can be improved by additives, and the elasticity and adhesiveness can be adjusted by appropriately adjusting the composition of the resin and the thickness of the biocontact layer.

[0267] <Bioelectrode> The present invention also provides a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, wherein the biocontact layer is a cured product of the bioelectrode composition of the present invention described above.

[0268] The bioelectrode of the present invention will be described in detail below with reference to the drawings, but the present invention is not limited thereto.

[0269] FIG. 1 is a schematic cross-sectional view showing an example of the bioelectrode of the present invention. The bioelectrode 1 of FIG. 1 has a conductive substrate 2 and a biocontact layer 3 formed on the conductive substrate 2. The biocontact layer 3 is made of a cured product of the bioelectrode composition of the present invention. The biocontact layer 3 is made of a complex 5 of an ionic polymer and a silicone having T units and Q units. The biocontact layer 3 can further contain an adhesive resin 6 other than the complex 5 of the ionic polymer and a silicone having T units and Q units, and a conductive powder 4. Hereinafter, with reference to FIGS. 1 and 2, a case will be described in which the biocontact layer 3 is a layer in which the complex 5 of the ionic polymer and a silicone having T units and Q units and the conductive powder 4 are dispersed in the adhesive resin 6, but the bioelectrode of the present invention is not limited to this embodiment.

[0270] When using such a bioelectrode 1 of Fig. 1, as shown in Fig. 2, the biocontact layer 3 (i.e., a layer in which a complex 5 of an ionic polymer, a silicone having T units and Q units, and a conductive powder 4 are dispersed in an adhesive resin 6) is brought into contact with a living body 7, and an electrical signal is extracted from the living body 7 by the complex 5 of an ionic polymer, a silicone having T units and a conductive powder 4, and the electrical signal is conducted to a sensor device or the like (not shown) via the conductive substrate 2. In this way, the bioelectrode of the present invention can achieve both electrical conductivity and biocompatibility by the complex of the ionic polymer, a silicone having T units and Q units, and has adhesiveness, so that the contact area with the skin is constant, and electrical signals from the skin can be obtained stably and with high sensitivity.

[0271] Each of the constituent materials of the bioelectrode of the present invention will be described in more detail below.

[0272] [Conductive base material] The bioelectrode of the present invention has a conductive substrate. This conductive substrate is usually electrically connected to a sensor device or the like, and conducts an electrical signal extracted from a living body via a living body contact layer to the sensor device or the like.

[0273] The conductive substrate is not particularly limited as long as it has conductivity, but it is preferable that the conductive substrate contains at least one material selected from the group consisting of gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and conductive polymers.

[0274] The conductive substrate is not particularly limited and may be a hard conductive substrate, a flexible conductive film, a fabric coated with a conductive paste, or a fabric with a conductive polymer kneaded in. The conductive substrate may be flat or uneven, or may be a mesh of woven metal wires, and may be appropriately selected depending on the application of the bioelectrode.

[0275] [Bio-contact layer] The bioelectrode of the present invention has a biocontact layer formed on a conductive substrate. This biocontact layer is the part that actually comes into contact with the living body when the bioelectrode is used, and has electrical conductivity and adhesiveness. The biocontact layer is a cured product of the bioelectrode composition of the present invention described above, that is, an adhesive resin layer made of a cured product of a composition containing the above-mentioned component (A) and, if necessary, components (B), (C), (D), (E), and (F).

[0276] The adhesive strength of the living body contact layer is preferably in the range of 0.01 N / 25 mm to 20 N / 25 mm. The adhesive strength is generally measured by the method shown in JIS Z 0237. A metal substrate such as SUS (stainless steel) or a PET (polyethylene terephthalate) substrate can be used as the substrate, but human skin can also be used for measurement. The surface energy of human skin is lower than that of metals and various plastics, and is close to that of Teflon (registered trademark), making it difficult to adhere to the skin.

[0277] The thickness of the biocontact layer of the bioelectrode is preferably 1 μm to 5 mm, more preferably 2 μm to 3 mm. The thinner the biocontact layer, the weaker the adhesive strength, but the more flexible it is, the lighter it is, and the better it fits to the skin. The thickness of the biocontact layer can be selected based on the balance between adhesiveness and texture on the skin.

[0278] In addition, in the bioelectrode of the present invention, similar to conventional bioelectrodes (for example, the bioelectrode described in JP 2004-033468 A), a separate adhesive film may be provided on the biocontact layer to prevent the bioelectrode from peeling off from the living body during use. When providing a separate adhesive film, it is sufficient to form the adhesive film using an adhesive film material such as an acrylic type, a urethane type, or a silicone type. In particular, the silicone type has high oxygen permeability, so that the skin can breathe while it is attached, and has high water repellency, so that the adhesiveness is less likely to decrease due to sweat, and further, is less irritating to the skin, so it is preferable. In addition, in the bioelectrode of the present invention, as described above, peeling off from the living body can be prevented by adding an adhesive imparting agent to the bioelectrode composition or using a resin that has good adhesiveness to the living body, so that the above-mentioned separate adhesive film is not necessarily required.

[0279] When the bioelectrode of the present invention is used as a wearable device, the wiring between the bioelectrode and the sensor device and other components are not particularly limited, and for example, those described in JP 2004-033468 A can be applied.

[0280] As described above, the bioelectrode of the present invention has a biocontact layer formed of the cured product of the bioelectrode composition of the present invention, so that the bioelectrode can efficiently transmit electrical signals from the skin to the device (i.e., has excellent electrical conductivity), is not likely to cause allergies even when worn on the skin for a long period of time (i.e., has excellent biocompatibility), is lightweight, can be manufactured at low cost, and does not significantly decrease in electrical conductivity even when wet or dried. In addition, the electrical conductivity can be further improved by adding a conductive powder, and a bioelectrode with particularly high adhesive strength and high elasticity can be manufactured by combining it with a resin having adhesiveness and elasticity. Furthermore, the elasticity and adhesiveness to the skin can be improved by additives, and the elasticity and adhesiveness can be adjusted by appropriately adjusting the composition of the resin and the thickness of the biocontact layer. Therefore, such a bioelectrode of the present invention is particularly suitable as a bioelectrode used in a medical wearable device.

[0281] <Manufacturing method of bioelectrodes> The present invention also provides a method for manufacturing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, in which the bioelectrode composition of the present invention described above is applied to the conductive substrate and cured to form the biocontact layer.

[0282] The conductive substrate and the like used in the method for producing a bioelectrode of the present invention may be the same as those described above.

[0283] The method for applying the bioelectrode composition onto the conductive substrate is not particularly limited, but suitable methods include, for example, dip coating, spray coating, spin coating, roll coating, flow coating, doctor coating, screen printing, flexographic printing, gravure printing, and inkjet printing.

[0284] The resin curing method is not particularly limited and may be appropriately selected depending on the components (A) and (B) used in the bioelectrode composition, but it is preferable to cure the resin by, for example, heat or light, or both. In addition, a catalyst that generates an acid or base may be added to the bioelectrode composition to cause a crosslinking reaction and cure the resin.

[0285] The temperature for heating is not particularly limited and may be appropriately selected depending on the components (A) and (B) used in the bioelectrode composition, but is preferably about 50 to 250°C, for example.

[0286] In addition, when heating and light irradiation are combined, heating and light irradiation may be performed simultaneously, or heating may be performed after light irradiation, or light irradiation may be performed after heating. In addition, air drying may be performed before heating after coating in order to evaporate the solvent.

[0287] After the film has hardened, applying water droplets or spraying water vapor or mist on the surface improves its compatibility with the skin, allowing for quick biosignals to be obtained. Water mixed with alcohol can also be used to reduce the size of the vapor or mist droplets. The film surface can also be wetted by contacting it with absorbent cotton or cloth soaked in water.

[0288] The water that wets the surface of the cured film may contain a salt, and the water-soluble salt that is mixed with the water is selected from sodium salts, potassium salts, calcium salts, magnesium salts, and betaines.

[0289] Specifically, the water-soluble salt may be a salt selected from sodium chloride, potassium chloride, calcium chloride, magnesium chloride, saccharin sodium salt, acesulfame potassium, sodium carboxylate, potassium carboxylate, calcium carboxylate, sodium sulfonate, potassium sulfonate, calcium sulfonate, sodium phosphate, potassium phosphate, calcium phosphate, magnesium phosphate, and betaine. Note that the above-mentioned components (A) and (C) are not included in the water-soluble salt.

[0290] More specifically, in addition to the above, sodium acetate, sodium propionate, sodium pivalate, sodium glycolate, sodium butyrate, sodium valerate, sodium caproate, sodium enanthate, sodium caprylate, sodium pelargonate, sodium caprate, sodium undecylate, sodium laurate, sodium tridecylate, sodium myristate, sodium pentadecylate, sodium palmitate, sodium margarate, sodium stearate, sodium benzoate, disodium adipate, disodium maleate, disodium phthalate, sodium 2-hydroxybutyrate, sodium 3-hydroxybutyrate, sodium 2-oxobutyrate, sodium gluconate, methane Examples of betaines include sodium sulfonate, sodium 1-nonanesulfonate, sodium 1-decanesulfonate, sodium 1-dodecanesulfonate, sodium 1-undecanesulfonate, sodium cocoyl ethionate, sodium lauroyl methyl alanine, sodium cocoyl methyl taurate, sodium cocoyl glutamate, sodium cocoyl sarcosine, sodium lauroyl methyl taurate, laumidopropyl betaine, potassium isobutyrate, potassium propionate, potassium pivalate, potassium glycolate, potassium gluconate, potassium methanesulfonate, calcium stearate, calcium glycolate, calcium gluconate, calcium 3-methyl-2-oxobutyrate, and calcium methanesulfonate. Betaine is a general term for intramolecular salts, specifically a compound in which three methyl groups are added to the amino group of an amino acid, and more specifically, trimethylglycine, carnitine, and proline betaine can be mentioned.

[0291] The water that wets the surface of the cured film may further contain a monohydric alcohol or polyhydric alcohol having 1 to 4 carbon atoms. The alcohol is preferably selected from ethanol, isopropyl alcohol, ethylene glycol, diethylene glycol, triethylene glycol, glycerin, polyethylene glycol, polypropylene glycol, polyglycerin, diglycerin, or a silicone compound having a polyglycerin structure, and it is more preferable that the silicone compound having a polyglycerin structure is one represented by the above general formula (4)' or (5)'.

[0292] The pretreatment method using a water-soluble salt-containing aqueous solution can wet the bioelectrode membrane after hardening by spraying, dispensing water droplets, etc. It can also be wetted in a high temperature and high humidity state such as a sauna. After wetting, in order to prevent drying, a protective film can be further laminated on the permeation layer to cover it. Since the protective film needs to be peeled off just before applying it to the skin, it can be coated with a release agent or a peelable Teflon (registered trademark) film can be used. For long-term storage, the dry electrode covered with the release film is preferably sealed in a bag covered with aluminum or the like. In order to prevent drying in the aluminum-covered bag, it is preferable to seal moisture in it.

[0293] Before attaching the bioelectrode of the present invention to the skin, the skin side can be moistened with water, alcohol, etc., or the skin can be wiped with a cloth or absorbent cotton containing water, alcohol, etc. The above-mentioned salt can also be contained in the water or alcohol.

[0294] As described above, the manufacturing method of the bioelectrode of the present invention makes it possible to easily manufacture, at low cost, the bioelectrode of the present invention which has excellent conductivity and biocompatibility, is lightweight, and whose conductivity does not decrease significantly whether it is wetted with water or dried. EXAMPLES

[0295] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these. In the following, "Me" represents a methyl group and "Vi" represents a vinyl group.

[0296] (ionic intermediate polymer) Ionic intermediate polymers 1 to 15 for obtaining the ionic polymer composite silicone described below, which is the component (A) of the present invention and is blended as an ionic material (conductive material) in the bioelectrode composition solution, were synthesized as follows. A 30% by mass cyclopentanone solution of each monomer was placed in a reaction vessel and mixed, the reaction vessel was cooled to -70°C under a nitrogen atmosphere, and degassed under reduced pressure and nitrogen blowing were repeated three times. After heating to room temperature, 0.02 mol of azobisisobutyronitrile (AIBN) was added as a polymerization initiator per mol of the total monomers, and the mixture was heated to 60°C and reacted for 15 hours. The composition of the obtained polymer was as follows, after drying the solvent: 1 The molecular weight (Mw) and dispersity (Mw / Mn) of the obtained polymer were confirmed by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent. The ionic intermediate polymers 1 to 15 having alkoxysilyl groups thus synthesized are shown below.

[0297] Ionic intermediate polymer 1 Mw=14,600 Mw / Mn=1.81 [ka]

[0298] Ionic intermediate polymer 2 Mw=16,600 Mw / Mn=1.65 [ka]

[0299] Ionic intermediate polymer 3 Mw=15,400 Mw / Mn=1.81 [ka]

[0300] Ionic intermediate polymer 4 Mw=16,500 Mw / Mn=1.79 [ka] (The number of repetitions in the formula indicates the average value.)

[0301] Ionic intermediate polymer 5 Mw=20,100 Mw / Mn=1.78 [ka]

[0302] Ionic intermediate polymer 6 Mw=27,400 Mw / Mn=1.91 [ka]

[0303] Ionic intermediate polymer 7 Mw=42,100 Mw / Mn=2.11 [ka] (The number of repetitions in the formula indicates the average value.)

[0304] Ionic intermediate polymer 8 Mw=17,100 Mw / Mn=1.88 [ka] (The number of repetitions in the formula indicates the average value.)

[0305] Ionic intermediate polymer 9 Mw=15,500 Mw / Mn=1.87 [ka] (The number of repetitions in the formula indicates the average value.)

[0306] Ionic intermediate polymer 10 Mw=21,500 Mw / Mn=1.70 [ka]

[0307] Ionic intermediate polymer 11 Mw=16,500 Mw / Mn=1.96 [ka]

[0308] Ionic intermediate polymer 12 Mw=21,500 Mw / Mn=1.75 [ka]

[0309] Ionic intermediate polymer 13 Mw=13,100 Mw / Mn=1.55 [ka] (The number of repetitions in the formula indicates the average value.)

[0310] Ionic intermediate polymer 14 Mw=17,500 Mw / Mn=1.83 [ka] (The number of repetitions in the formula indicates the average value.)

[0311] Ionic intermediate polymer 15 Mw=19,600 Mw / Mn=1.87 [ka] (The number of repetitions in the formula indicates the average value.)

[0312] Blended ionic polymer 1, comparative ionic intermediate polymer 1 for comparison, and comparative ionic polymer composite silicone 2-1 are shown below.

[0313] Blended ionic polymer 1 Mw=39,100 Mw / Mn=1.91 [ka] (The number of repetitions in the formula indicates the average value.)

[0314] Comparative ionic intermediate polymer 1 Mw=26,900 Mw / Mn=1.99 [ka]

[0315] Comparison Ionic Polymer Composite Silicone 2-1 Mw=22,300 Mw / Mn=1.98 [ka]

[0316] (Ionic polymer composite silicone) 100 g of a cyclopentanone solution of the ionic intermediate polymer 1 obtained by the polymerization was added to 10 g of pure water and 0.1 g of nitric acid in a 0.5 L glass flask, and the mixture was stirred at 40° C. for 8 hours. After that, 30 g of cyclopentanone was added, and the mixture was concentrated under reduced pressure and dehydrated and denitrified at the same time, to obtain a cyclopentanone solution containing 30 mass % of ionic polymer composite silicone 1-1.

[0317] Ionic polymer composite silicone 1-1 Mw=23,600 Mw / Mn=2.35 [ka]

[0318] In the same manner, ionic polymer composite silicone 2-1 to ionic polymer composite silicone 15-1 and comparative ionic polymer composite silicone 1-1 were synthesized. Ionic polymer composite silicone 8-2 was co-condensed with vinyltrimethoxysilane, ionic polymer composite silicone 8-3 was co-condensed with allyltrimethoxysilane, ionic polymer composite silicone 13-1 was co-condensed with tetramethoxysilane, and ionic polymer composite silicones 13-2 to 15-1 were co-condensed with trimethoxysilane having a cyano group, a nitro group, a potassium salt of fluorosulfonic acid, a sodium salt of fluorosulfonimide, and a potassium salt of n-carbonylfluorosulfonamide, respectively.

[0319] Ionic polymer composite silicone 2-1 Mw=39,100 Mw / Mn=3.12 [ka]

[0320] Ionic polymer composite silicone 3-1 Mw=23,400 Mw / Mn=2.61 [ka]

[0321] Ionic polymer composite silicone 4-1 Mw=21,500 Mw / Mn=2.23 [ka] (The number of repetitions in the formula indicates the average value.)

[0322] Ionic polymer composite silicone 5-1 Mw=33,100 Mw / Mn=2.68 [ka]

[0323] Ionic polymer composite silicone 6-1 Mw=35,100 Mw / Mn=2.88 [ka]

[0324] Ionic polymer composite silicone 7-1 Mw=57,900 Mw / Mn=3.93 [ka] (The number of repetitions in the formula indicates the average value.)

[0325] Ionic polymer composite silicone 8-1 Mw=32,100 Mw / Mn=3.11 [ka] (The number of repetitions in the formula indicates the average value.)

[0326] Ionic polymer composite silicone 8-2 Mw=35,100 Mw / Mn=3.31 [ka] (The number of repetitions in the formula indicates the average value.)

[0327] Ionic polymer composite silicone 8-3 Mw=35,800 Mw / Mn=3.38 [ka] (The number of repetitions in the formula indicates the average value.)

[0328] Ionic polymer composite silicone 9-1 Mw=37,500 Mw / Mn=3.13 [ka]

[0329] Ionic polymer composite silicone 10-1 Mw=25,600 Mw / Mn=2.88 [ka]

[0330] Ionic polymer composite silicone 11-1 Mw=23,500 Mw / Mn=2.46 [ka]

[0331] Ionic polymer composite silicone 12-1 Mw=32,500 Mw / Mn=2.75 [ka]

[0332] Ionic polymer composite silicone 13-1 Mw=35,100 Mw / Mn=3.35 [ka]

[0333] Ionic polymer composite silicone 13-2 Mw=38,100 Mw / Mn=3.77 [ka] (The number of repetitions in the formula indicates the average value.)

[0334] Ionic polymer composite silicone 13-3 Mw=35,700 Mw / Mn=3.66 [ka] (The number of repetitions in the formula indicates the average value.)

[0335] Ionic polymer composite silicone 13-4 Mw=36,100 Mw / Mn=3.95 [ka] (The number of repetitions in the formula indicates the average value.)

[0336] Ionic polymer composite silicone 13-5 Mw=38,400 Mw / Mn=3.69 [ka] (The number of repetitions in the formula indicates the average value.)

[0337] Ionic polymer composite silicone 13-6 Mw=38,800 Mw / Mn=3.94 [ka] (The number of repetitions in the formula indicates the average value.)

[0338] Ionic polymer composite silicone 13-7 Mw=36,300 Mw / Mn=3.96 [ka] (The number of repetitions in the formula indicates the average value.)

[0339] Ionic polymer composite silicone 13-8 Mw=33,600 Mw / Mn=4.22 [ka] (The number of repetitions in the formula indicates the average value.)

[0340] Ionic polymer composite silicone 14-1 Mw=31,700 Mw / Mn=3.64 [ka] (The number of repetitions in the formula indicates the average value.)

[0341] Ionic polymer composite silicone 15-1 Mw=36,800 Mw / Mn=4.13 [ka] (The number of repetitions in the formula indicates the average value.)

[0342] Comparison Ionic Polymer Composite Silicone 1-1 Mw=46,000 Mw / Mn=3.02 [ka]

[0343] Siloxane compounds 1 to 4 that were blended as silicone resins in the bioelectrode composition solution are shown below.

[0344] (Siloxane Compound 1) The viscosity of a 30% toluene solution was 27,000 mPa·s, the alkenyl group content was 0.007 mol / 100 g, and the vinyl group-containing polydimethylsiloxane whose molecular chain ends were blocked with SiMe2Vi groups was designated as siloxane compound 1.

[0345] (Siloxane Compound 2) Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A 60% toluene solution of siloxane compound 2 (SiO2 unit / SiO2 unit = 0.8) was used as the siloxane compound 2.

[0346] (Siloxane Compound 3) 40 parts by mass of vinyl-containing polydimethylsiloxane whose molecular chain ends are capped with OH, whose viscosity in a 30% toluene solution is 42,000 mPa s and whose alkenyl group content is 0.007 mol / 100 g, Me3SiO 0.5 Polysiloxane (Me3SiO 0.5 A solution consisting of 100 parts by mass of a 60% toluene solution of 1,2-dichloro-2,4-diphenyl-2,4-tetramethylphenyl-2,5-diphenyl-2,6-diphenyl-2,7-diphenyl-2,8-diphenyl-2,7-diphenyl-2,8-diphenyl-2,6-diphenyl-2,7 ...

[0347] (Siloxane Compound 4) As the methyl hydrogen silicone oil, KF-99 manufactured by Shin-Etsu Chemical Co., Ltd. was used.

[0348] The silicone pendant urethane acrylate 1 blended in the bioelectrode composition solution is shown below. [ka] (The number of repetitions in the formula indicates the average value.)

[0349] The acrylic polymer 1 blended as the acrylic resin in the bioelectrode composition solution is shown below.

[0350] Acrylic Polymer 1 Mw=127,000 Mw / Mn=2.28 [ka] (The number of repetitions in the formula indicates the average value.)

[0351] Polyglycerin silicone compound 1 is shown below.

[0352] [ka]

[0353] The organic solvents contained in the bioelectrode composition solution are shown below. EDE: Diethylene glycol diethyl ether Isopar G: Isoparaffinic solvent, manufactured by Standard Oil Isopar M: Isoparaffinic solvent, manufactured by Standard Oil

[0354] The lithium titanate powder, radical generator, platinum catalyst, and conductivity enhancer (carbon black, carbon nanotubes, graphite, and metal powder) that were blended as additives in the bioelectrode composition solution are shown below. Lithium titanate powder, spinel: Sigma-Aldrich, size 200nm or less Radical generator: BASF Irgacure TPO Platinum catalyst: CAT-PL-50T manufactured by Shin-Etsu Chemical Co., Ltd. Carbon black: Denka Black Li-400 manufactured by Denka Multi-walled carbon nanotubes: Sigma-Aldrich, diameter 110-170 nm, length 5-9 μm Graphite: Sigma-Aldrich, diameter 20 μm or less Metal powder Silver powder: Sigma-Aldrich silver flakes, diameter 10 μm

[0355] [Examples 1 to 26, Comparative Examples 1 to 3] Ionic polymer composite silicone, resin, ionic polymer, organic solvent, and additives (radical generator, platinum catalyst, conductivity enhancer, etc.) were blended in the compositions shown in Tables 1 to 3 to prepare bioelectrode composition solutions (bioelectrode composition solutions 1 to 26, comparative bioelectrode composition solutions 1 to 3).

[0356] [Table 1]

[0357] [Table 2]

[0358] [Table 3]

[0359] (Adhesiveness evaluation) Bioelectrode composition solutions 1 to 15, 17 to 26 and comparative bioelectrode composition solutions 1 to 3 were applied to a 100 μm thick PEN (polyethylene naphthalate) substrate using an applicator, air-dried at room temperature for 30 minutes, and then baked in an oven at 120° C. for 10 minutes in a nitrogen atmosphere to harden the solution, producing an adhesive film. Bioelectrode composition solution 16 was applied, air-dried and baked, and then cured at 500 mJ / cm 2 with a 1,000 W xenon lamp in a nitrogen atmosphere. 2 The composition coating was cured by irradiation with light of 100 .mu.m to prepare an adhesive film.

[0360] A 25 mm wide tape was cut from this adhesive film, pressed onto a stainless steel plate (SUS304), and left at room temperature for 20 hours. The force (N / 25 mm) required to peel the tape from the stainless steel plate was then measured using a tensile tester at an angle of 180 degrees and at a speed of 300 mm / min. The results are shown in Table 4.

[0361] (Preparation of bioelectrodes) As shown in FIG. 3, a conductive paste manufactured by Fujikura Kasei, Dotite FA-333, was coated on ST-604 of a thermoplastic urethane (TPU) film 20 manufactured by Bemis by screen printing, and baked in an oven at 120°C for 10 minutes to print a keyhole-shaped conductive pattern 2 with a circle diameter of 2 cm. A bioelectrode composition solution shown in Tables 1 to 3 was applied by screen printing on the circular part on top of the conductive pattern, and air-dried at room temperature for 10 minutes, and then baked in an oven at 125°C for 10 minutes to evaporate the solvent and harden the film, forming a biocontact layer 3, which was used as a bioelectrode 1. Furthermore, in Example 16, a xenon lamp was used in a nitrogen atmosphere at 200 mJ / cm 2 Next, as shown in Fig. 4, the thermoplastic urethane film 20 on which the bioelectrode 1 was printed was cut out, and a double-sided tape 21 was attached to it, to prepare three bioelectrode samples 10 for each composition solution.

[0362] (Measurement of the thickness of the biological contact layer) The thickness of the biocontact layer of the bioelectrode prepared above was measured using a micrometer. The results are shown in Table 4.

[0363] (Measurement of biological signals) The conductive wiring pattern made of conductive paste of the bioelectrode was connected with a portable electrocardiograph HCG-901 manufactured by Omron Healthcare Co., Ltd. with a conductive wire, and the positive electrode of the electrocardiograph was attached to the LA position of the human body in Figure 5, the negative electrode to the LL position, and the earth to the RA position. Immediately after attachment, electrocardiogram measurement was started, and the time until the electrocardiogram waveform (ECG signal) consisting of P, Q, R, S, and T waves shown in Figure 6 appeared was measured. The results are shown in Table 4.

[0364] [Table 4]

[0365] As shown in Table 4, in Examples 1 to 26 in which the biocontact layer was formed using the bioelectrode composition of the present invention containing an ionic polymer and a complex of T unit silicone, the adhesiveness was excellent, and a biosignal could be obtained in a short time after application to the body. On the other hand, in the case of Comparative Example 2 in which an ionic component of a specific structure was not contained, a biosignal could not be obtained. In addition, in the case of Comparative Example 1 in which only a blended ionic polymer was added, or in the case of Comparative Example 3 in which an ionic polymer of a complex with a cage-type T unit silicone was added, the adhesiveness was low, and it took a long time for a biosignal to appear after application to the skin.

[0366] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention. [Explanation of symbols]

[0367] 1...bioelectrode, 2...conductive substrate (conductive pattern), 3...biocontact layer, 4...conductive powder, 5...complex of ionic polymer and silicone having T units and Q units, 6: adhesive resin; 7: living body; 10: living body electrode sample; 20...thermoplastic urethane film, 21...double-sided tape.

Claims

1. A bioelectrode composition comprising: (A) A silicone bonded to an ionic polymer and having a structure (excluding a cage structure) containing a T unit represented by the following general formula (T1): (R 0 Yes 3/2 ) (T1) (In the formula, R 0 is a linking group to the ionic polymer. and the ionic polymer is a polymer having a repeating unit having a structure selected from the group consisting of an ammonium salt, a lithium salt, a sodium salt, a potassium salt, and a silver salt of any one of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide; The repeating unit having a structure selected from the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide is one or more selected from repeating units (2-1) to (2-7) represented by the following general formula (2), and The bioelectrode composition, characterized in that the component (A) is a condensation reaction product of an ionic intermediate polymer in which, in addition to the repeating unit described in the general formula (2), a repeating unit having an alkoxysilyl group described in the following general formula (3) is copolymerized: 【Chemistry 1】 (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group; R 2 , R 4 , R 6 , R 9 , R 12 and R 14 are each independently a single bond, or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have either an ester group or an ether group, or both; R 7 is a linear or branched alkylene group having 1 to 4 carbon atoms, and one or two of the hydrogen atoms in R 7 may be substituted with a fluorine atom; X 1 , X 2 , X 3 , X 4 , X 6 and X 7 are each independently a single bond, a phenylene group, a naphthylene group, an ether group, an ester group or an amide group; X 5 is a single bond, an ether group, or an ester group. Y is an oxygen atom or a -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms, which may be bonded to R 4 to form a ring. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6, and a7 are 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, and 0<a1+a2+a3+a4+a5+a6+a7≦1.

0. M + is an ion selected from an ammonium ion, a lithium ion, a sodium ion, a potassium ion, and a silver ion. Rf 5 , Rf 6 , and Rf 7 is a fluorine atom or a linear or branched alkyl group having 1 to 4 carbon atoms and having at least one fluorine atom. 【Chemistry 2】 (In the formula, R 20 is a hydrogen atom or a methyl group, X 8 is a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group, R 21 is a single bond, a linear, branched or cyclic alkylene group having 1 to 10 carbon atoms, or a phenylene group, which may contain an oxygen atom or a nitrogen atom, R 22 is the same or different alkyl groups having 1 to 4 carbon atoms, and b1 is 0<b1<1.0.)

2. 2. The bioelectrode composition according to claim 1, wherein the condensation reaction product has a repeating unit represented by the following general formula (4): 【Chemistry 3】 (In the formula, R 20 , X 8 , R 21 , and b1 are as described above.)

3. The bioelectrode composition according to claim 1 or 2, characterized in that the component (A) contains an ammonium ion represented by the following general formula (5) as an ammonium ion constituting the ammonium salt: 【Chemistry 4】 (In the formula, R 101d , R 101e , R 101f , R 101g R each represents a hydrogen atom, a linear, branched, or cyclic alkyl group having 1 to 13 carbon atoms, a linear, branched, or cyclic alkenyl or alkynyl group having 2 to 12 carbon atoms, or an aromatic group having 4 to 20 carbon atoms, and may have one or more groups selected from an ether group, a carbonyl group, an ester group, a hydroxy group, an amino group, a nitro group, a sulfonyl group, a sulfinyl group, a halogen atom, and a sulfur atom. 101d and R 101e , R 101d and R 101e and R 101f may form a ring together with the nitrogen atom to which they are attached, and when they form a ring, R 101d and R 101e and R 101d and R 101e and R 101f is an alkylene group having 3 to 10 carbon atoms, or forms a heteroaromatic ring having the nitrogen atom in the ring.

4. The bioelectrode composition according to any one of claims 1 to 3, further comprising an adhesive resin as component (B).

5. 5. The bioelectrode composition according to claim 4, wherein the component (B) is at least one selected from the group consisting of silicone resins, (meth)acrylate resins, and urethane resins.

6. 6. The bioelectrode composition according to claim 4, characterized in that the component (B) contains a diorganosiloxane having an alkenyl group and an organohydrogenpolysiloxane having a SiH group.

7. The component (B) further includes R x SiO (4-x)/2 units (R is a substituted or unsubstituted monovalent hydrocarbon group having 1 to 10 carbon atoms, and x is in the range of 2.5 to 3.5) and SiO 2 7. The bioelectrode composition according to claim 6, which contains a silicone resin having a unit.

8. 8. The bioelectrode composition according to claim 1, further comprising a polymer compound having an ionic repeating unit as component (C).

9. The ionic repeating unit of the component (C) is represented by the following general formula (2): fluorosulfonic acid, fluorosulfonimide, and N-carbonylfluorosulfonamide. The bioelectrode composition according to claim 8, characterized in that it contains a repeating unit having a structure selected from the ammonium salt, lithium salt, sodium salt, potassium salt, and silver salt of any of these. 【Chemistry 5】 (In the formula, R 1 , R 3 , R 5 , R 8 , R 10 , R 11 and R 13 are each independently a hydrogen atom or a methyl group, R 2 , R 4 , R 6 , R 9 , R 12 and R 14 R each independently represents a single bond, or a linear, branched or cyclic hydrocarbon group having 1 to 13 carbon atoms which may have either an ester group or an ether group, or both. 7 is a linear or branched alkylene group having 1 to 4 carbon atoms; R 7 One or two of the hydrogen atoms in X may be substituted with a fluorine atom. 1 , X 2 , X 3 , X 4 , X 6 , and X 7 each independently represents a single bond, a phenylene group, a naphthylene group, an ether group, an ester group, or an amide group; X 5 is a single bond, an ether group, or an ester group. Y is an oxygen atom, -NR 19 - group, and R 19 is a hydrogen atom or a linear or branched alkyl group having 1 to 4 carbon atoms; R 4 may be bonded to form a ring. m is an integer of 1 to 4. a1, a2, a3, a4, a5, a6 and a7 are within the ranges of 0≦a1≦1.0, 0≦a2≦1.0, 0≦a3≦1.0, 0≦a4≦1.0, 0≦a5≦1.0, 0≦a6≦1.0, 0≦a7≦1.0, and 0<a1+a2+a3+a4+a5+a6+a7≦1.

0. M + is an ion selected from an ammonium ion, a lithium ion, a sodium ion, a potassium ion, and a silver ion. 5 , Rf 6 , Rf 7 is a fluorine atom or a linear or branched alkyl group having 1 to 4 carbon atoms and having at least one fluorine atom.

10. The bioelectrode composition according to any one of claims 1 to 9, further comprising carbon powder and / or metal powder as component (D).

11. 11. The bioelectrode composition according to claim 10, wherein the carbon powder is either or both of carbon black and carbon nanotubes.

12. 12. The bioelectrode composition according to claim 10, wherein the metal powder is selected from the group consisting of gold, silver, platinum, copper, tin, titanium, nickel, aluminum, tungsten, molybdenum, ruthenium, chromium, and indium.

13. 13. The bioelectrode composition according to claim 12, wherein the metal powder is silver powder.

14. The bioelectrode composition according to any one of claims 1 to 13, further comprising an organic solvent as component (E).

15. A bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, the bioelectrode being characterized in that the biocontact layer is a cured product of the bioelectrode composition according to any one of claims 1 to 14.

16. The bioelectrode according to claim 15, characterized in that the conductive base material contains one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and conductive polymers.

17. A method for manufacturing a bioelectrode having a conductive substrate and a biocontact layer formed on the conductive substrate, comprising applying a bioelectrode composition according to any one of claims 1 to 14 onto the conductive substrate and curing the composition to form the biocontact layer.

18. The method for manufacturing a bioelectrode according to claim 17, characterized in that the conductive base material contains one or more selected from gold, silver, silver chloride, platinum, aluminum, magnesium, tin, tungsten, iron, copper, nickel, stainless steel, chromium, titanium, carbon, and conductive polymers.

Citation Information

Patent Citations

  • Conductive millable urethane rubber electrode

    JP1993095924A

  • Silicone rubber composition for living body electrode and electrode for living body

    JP2003225217A

  • Long-life conjugated polymer electrochemical device incorporating ionic liquid

    JP2004527902A

  • Composition for coating formation used for formation of transparent conductive film

    JP2013016455A

  • Biocompatible electrode structure and manufacturing method therefor, and device and manufacturing method therefor

    JP2015019806A